A mechanically stable and kinetically optimized organic-inorganic hybrid SEI for ultra-long lifespan zinc metal anodes - Chenyi Cao; Dan Lu; Chao Li; Xin Tan; Tianci Li; Shoubin Zhou; Xueping Tang; Sean C. Smith; Zhao Fu; Hongjia Song; Yunya Liu; Xiangli Zhong; et al. (Chemical Engineering Journal, 2026)

Climate-induced forest destabilization and shrub stabilization in Africa - Linhai Cheng; Qiang Tang; Nan Lu; Yafeng Wang; Changjia Li; Shuai Wang; Xiangyi Li; Phuping Sucharitakul; Yongzhe Chen; Zhihong Xu; Lindsay C. Stringer; Bojie Fu (Global and Planetary Change, 2026)

Characteristics of metals and Pb isotope ratios in PM2.5 emitted from temples and their impact on ambient air across different seasons and visitor numbers - Chien-Cheng Jung; Yi Kao; Charles C.-K. Chou; Nai-Tzu Chen; Yi-Tang Huang (Environmental Pollution, 2026)

Advanced nitrogen removal system coupling partial nitritation, anammox, denitrification and oxygen-permeable hollow-fibre membranes for precise oxygen regulation - Xifang Tang; Bao-Shan Xing; Yong-Ning Feng; Liguo Wan; Ling-Hu Li; Xin-Xin Sun; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Comparative soil organic matter prediction in Chinese mollic-phaeozems and Argentine chromic-phaeozems using a colorimeter and portable X-ray fluorescence - Jun Jiang; Feng Zhang; Kang Tian; Le Jian; Wenyou Hu; Yiyi Deng; Zhimin Tang; Yiping Zhu; Diego S. Fernández; Daniela C. Villegas; Biao Huang (Geoderma Regional, 2026)

Determinants of physiological demands, physiological resilience, and muscle fatigability during load carriage in women: an observational trial - Erin E. Robertson; Charlotte V. Coombs; Ella B. Halsall; Christina D. Young; Alice S. Irving; Jonathan C. Y. Tang; Julie P. Greeves; Thomas J. O’Leary (European Journal of Applied Physiology, 2026)

Integrated analysis of PM2.5-bound metals and associated sources to investigate the representativeness of atmospheric PM2.5 data for residential exposure in industrial areas during high PM2.5 seasons - Chien-Cheng Jung; Yi-Jie Chung; Po-Hsuan Shao; Charles C.-K. Chou; Yi-Tang Huang (Environmental Research, 2026)

A Dataset of Tropical Cyclones in the Western North Pacific from Chinese Fengyun Geostationary Meteorological Satellite Observations over the Past Two Decades - Xiaoqin Lu; Johnny C. L. Chan; Jie Tang; Hui Yu; Feng Lu; Yue Wang; Ming Ying; Runling Yu; Lan Wei; Longping Hu (Advances in Atmospheric Sciences, 2026)
This paper introduces a comprehensive Tropical Cyclone (TC) dataset based on China’s FengYun (FY) series geostationary satellite observations in the Western North Pacific (WNP), designated as FYSATTY. This innovative dataset integrates high-resolution geostationary meteorological satellite observations with best-track data, providing a unique resource for TC monitoring and analysis in the WNP region. FYSATTY is derived from infrared, water vapor, and visible channel imagery captured by the FY-2 and FY-4 satellites, which is processed using an equal-interval latitude-longitude grid system within a 1500-km radius centered on each TC. The best-track data, sourced from the China Meteorological Administration (CMA), is interpolated into 3-h intervals to ensure temporal consistency with the satellite observations. This dataset consists of 99714 observations for 614 TCs from 2005 to 2024 and will be updated annually. It represents the most comprehensive collection of TC satellite imagery derived from the FY series of geostationary meteorological satellites of the National Satellite Meteorological Center (NSMC). It encompasses a synthesis of infrared, water vapor, and visible channel data from the FY-2 and FY-4 satellite series. The dataset has been meticulously cropped and georeferenced using the CMA best-track data, with fundamental geographic spatial calibration completed. Comparative analysis with analogous elements within other TC geostationary meteorological satellite datasets reveals a high degree of consistency. It is suitable for reanalyzing TC best-track data, assessing climatic characteristics of TC satellite observations, and enhancing forecasting capabilities. This dataset is particularly useful for TC research, forecasting, and machine learning, and is publicly available.

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Extraction of nickel, cobalt and copper from low grade finely disseminated polymetallic concentrates utilizing alkaline glycine and subsequent metal recovery from solution - C.G. Perea; T. Tang; C. He; A. Polenio; J.J. Eksteen (Hydrometallurgy, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Exploring hand hygiene practices in food businesses using the capability, opportunity and motivation for behaviour change (COM-B) model - Rana Kebbi; Claire Haven-Tang; Elizabeth C. Redmond; Ellen W. Evans (Food Control, 2026)

The impact of digital finance on ecological environment resilience in the Yangtze River Delta region - C. Zhu; C. Duan; D. Ma; Z. Wang; S. Tang (International Journal of Environmental Science and Technology, 2026)

Fluvial connectivity drives carbon cycle dynamics in a tropical mega‐delta - Adrian M. Bass; Wenguang Tang; Andrew C. G. Henderson; Virginia N. Panizzo; James Fielding; Abhra Chanda; Souvik Shil; Tuhin Ghosh; Charlotte Slaymark; Andy Large (Limnology and Oceanography, 2026)
Coastal estuaries are hotspots of biogeochemical cycling, biodiversity, and sediment processing, yet the drivers of carbon cycle processes remain poorly constrained. Here, we elucidate the influence of hydrological connectivity on carbon biogeochemistry in the Indian Sundarban over successive monsoon seasons by comparing hydrologically connected channels with perennial freshwater flow to channels isolated from feeding rivers. Results demonstrate dissolved organic carbon (DOC) and particulate organic carbon (POC) varied significantly with both season and connectivity. Dissolved organic carbon peaked pre‐monsoon and POC during the monsoon, with higher concentrations in hydrologically connected sites. Dissolved inorganic carbon (DIC) declined during the monsoon season but showed no connectivity effect. Elevated DOC relative to conservative mixing was attributed to freshwater runoff or groundwater input. Isotope data (δ 13 C) indicated POC respiration dominated during pre‐ and post‐monsoon, while DOC flocculation during the monsoon controlled POC dynamics, particularly in connected sites. Carbonate dissolution primarily regulated pre‐monsoon DIC, while organic matter degradation dominated in the monsoon and post‐monsoon periods. CO 2 efflux, measured across all sites, was consistently a source to the atmosphere and two to four times higher in connected channels, with higher turbulence driving maximum fluxes. Our findings demonstrate that hydrological connectivity fundamentally structures estuarine carbon cycling, lowering organic carbon concentrations and enhancing CO 2 fluxes. Shifts in global coastal delta sediment dynamics, in association with anthropogenic river management, therefore, have the potential to significantly alter delta carbon dynamics on a global scale.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Biofilm-inspired encapsulation enhances the viability of probiotic Lacticaseibacillus paracasei NN4–1 under simulated gastrointestinal conditions - Fedrick C. Mgomi; Chunlei Lu; Anqi Tang; Shu Xu; Fei Chen; Lei Yuan; Zhen-quan Yang (Food Research International, 2026)

Executive green perception, green technology innovation and enterprise biodiversity exposure: based on simultaneous equation model - C. Zhang; Z. Zhang; Z. Tang (International Journal of Environmental Science and Technology, 2026)

Divergent effects of straw and biochar on soil carbon priming are depth-dependent in subtropical Moso bamboo forests - Zhenhui Jiang; Shaobo Zhang; Caixian Tang; Mouliang Xiao; Jiashu Zhou; Yu Luo; Tida Ge; Bing Yu; Jason C. White; Yongfu Li (Biology and Fertility of Soils, 2026)

Dissimilarity among soil restoration practices influences soil functions and plant biomass: A functional group approach - Huiying Li; Anika Lehmann; Edda Kunze; Yaqi Xu; Bo Tang; Tingting Zhao; Rebecca Rongstock; Matthias C. Rillig (Agriculture, Ecosystems & Environment, 2026)

(+)-Catechin from Prunus padus disrupts detoxification pathways and provides field-level control of the bird cherry-oat aphid, Rhopalosiphum padi - Wenhua Hou; Xiaoxiao Yuan; Linhai Xia; Ni Wang; Hongcheng Tang; Jaime C. Piñero; Xiong Peng; Maohua Chen (Pesticide Biochemistry and Physiology, 2026)

PTUPB improves cognitive function in Alzheimer’s disease associated with enhancing cerebral vascular myogenic response and attenuating vascular remodeling - Gilbert C. Morgan; Andrew Gregory; Chengyun Tang; Sung Hee Hwang; Jane J. Border; Jing Xu; Yedan Liu; Shan Bai; Tae Jin Lee; Cameron Cantwell; David Bunn; Karen M. Wagner; et al. (GeroScience, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Function and mechanisms of polyethylene glycol-modified sodium acrylate-acrylamide hydrogel for microalgal biomass enrichment and purification - Cong-Cong Tang; Qiao Zhong; Yi Liu; Yong-Qi Cheng; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

In tribute to Francesco Di Virgilio, a great scientist and a wonderful friend - Simonetta Falzoni; Anna Lisa Giuliani; Elena Adinolfi; Robson Coutinho-Silva; Peter Illes; Simon C. Robson; Yong Tang; Henning Ulrich; Charles Kennedy (Purinergic Signalling, 2026)
Francesco Di Virgilio, one of the giants of purinergic signalling, died suddenly on September 22, 2024, which is an immense loss to so many friends and colleagues and especially to his beloved wife, Dorianna. Here, 1 year on, we pay tribute to him and his immense contribution to our field. Francesco graduated in medicine from the University of Padova, Italy, in 1979, with what became a lifelong interest in inflammation. He then held post-doctoral positions at University College London, Padova University, and Columbia University, New York, where he became acquainted with P2X7 receptors. He then returned to Padova as an Associate Professor of Molecular Pathology before moving to the University of Ferrara in 1992, where he set up a world-leading lab that studied the roles and underlying cellular mechanisms of the action of P2X7 receptors in inflammatory pathologies. Francesco published over 370 peer-reviewed articles, which have been cited > 35,000 times, giving him an H-index > 100. In addition, he filed several patents related to purinergic signalling. He also collaborated extensively, both within the University of Ferrara and worldwide, including in universities in the UK, Spain, Germany, the USA, and Brazil. Francesco was a man of great passion and intellect, who possessed scientific vision, intuition, and integrity, and he became the go-to world expert on P2X7 receptors and inflammation. We have lost a giant in the field and a dear friend, but he leaves behind an exceptional body of work, an outstanding legacy, and many friends who will miss him.

Industry Practices in Oligonucleotide Tissue Biodistribution Assessment: An IQ consortium Cross-Industry Survey of Current Approaches and Emerging Trends - Michael McCoy; Huaping Tang; Lydia Michaut; Irina Laczkovich; Girish Chopda; Linzhi Chen; Isha Taneja; C. Andrew Boswell; Guangnong Zhang (The AAPS Journal, 2026)
Accurate assessment of tissue distribution for oligonucleotide therapeutic (ONT) drug candidates is essential for understanding pharmacokinetic behavior and predicting therapeutic efficacy. ONTs present a unique challenge with their rapid systemic clearance coupled with prolonged tissue retention, making comprehensive tissue concentration evaluation critical for successful drug development. The IQ Consortium Tissue Concentration Working Group surveyed member companies about their current tissue concentration assessment methods to understand industry practices and identify areas for improvement. Most companies reported that ONTs still represent a relatively small portion of their pre-candidate selection portfolios, reflecting the evolving nature of this therapeutic modality. siRNAs dominated development efforts across surveyed organizations, followed by antisense oligonucleotides, indicating clear therapeutic class preferences within the industry. Assessment strategies varied considerably across organizations, highlighting different approaches to resource allocation and risk management. While some companies routinely evaluate tissue concentrations for all ONT programs regardless of indication or target, others take a more selective, program-dependent approach based on compound characteristics and therapeutic objectives. Despite this strategic variability, there was universal reliance on LC–MS for quantification, often supplemented with qPCR/RT-qPCR and hybridization assays for comprehensive analytical coverage. All surveyed companies integrate tissue concentration data into translational pharmacokinetic modeling efforts, yet few have adopted physiologically-based pharmacokinetic (PBPK) models as standard practice. Companies recognize the value of improving ONT tissue distribution assessment through standardized methodology tailored to specific oligonucleotide classes. Graphical Abstract

CFD prediction of ship motions and bow loads in short-crested irregular waves - Haoyun Tang; Deyuan Ren; Shan Wang; C. Guedes Soares (Ocean Engineering, 2026)

Optimal control of ventilation in enclosed spaces using Adversarial Neural Networks - Donghu Guo; Claire E. Heaney; Boyang Chen; Jieyi Tang; Andrea Cammarano; Prashant Kumar; Christopher C. Pain (Building and Environment, 2026)

Bifidobacterium breve BBr60 Enhances SCFA Levels and Restores NLRP3/NLRP6 Balance in the Gut to Improve Motor Deficits in PD Mice - P. P. An; X. Y. Liang; X. Y. Yao; Z. H. Liao; Y. C. Tang; N. Cao; Z. Wang; W. Wang; H. Y. Niu; C. X. Tang; J. Chen (Probiotics and Antimicrobial Proteins, 2026)

Biochar mitigates the suppressive effects of nitrogen deposition on soil methane uptake in a subtropical forest - Jiashu Zhou; Caixian Tang; Tony Vancov; Shenglei Fu; Yunying Fang; Tida Ge; Yanfei Dong; Yu Luo; Bing Yu; Yanjiang Cai; Jason C. White; Yongfu Li (Agriculture, Ecosystems & Environment, 2026)

Stressor Combinations Shift Soil Microbial Communities From Rare to Unknown Taxa and Alter Genomic Strategies - Shuxun Cheng; Xianjin Tang; Xing Huang; Yang Li; Shuyi Huang; Dan He; Eduardo Moreno‐Jiménez; Jianming Xu; Matthias C. Rillig; Zhongmin Dai; Manuel Delgado‐Baquerizo (Global Change Biology, 2026)
Soil microorganisms constitute the largest portion of Earth's biodiversity. However, soil microorganisms are also highly sensitive to on‐going global change, and the influence of an increasing number of stressors on common, rare, and unknown taxa across large environmental gradients remains virtually unknown. Here, we combined a large‐scale spatial field survey across multiple different ecosystems and found that the diversity and abundance of soil rare taxa were significantly reduced under high environmental stressor number (i.e., a high number of stressors passing a 75% stressor threshold). Strikingly, the abundance of unknown soil taxa and unknown genes increased with increasing environmental stress number. We further identified the metagenome‐assembled genomes (MAGs) that were considered as relatively common taxa using metagenomics. Compared to 9% of negative responders, 32% of common MAGs were resistant or positively responsive to multiple stress, displaying a reduced potential for cellular processes and an enhanced potential for environmental, genetic, and metabolic processes. Our study suggests that as stress increases, we would have less rare, but more unknown microorganisms and unique genomes of resistant common taxa, suggesting major changes in the soil microbiome in a world subjected to multiple global change stressors.

Seismic performance and fragility assessment of BRBFs subjected to sequential earthquakes - Tao Li; Shijie Shu; Kurtulus Atasever; Kaoshan Dai; Oguz C. Celik; Jun Tang (Soil Dynamics and Earthquake Engineering, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Biochar alleviates ammonium-induced suppression of methane uptake in a subtropical forest soil - Jiashu Zhou; Yanfei Dong; Caixian Tang; Zhenhui Jiang; Xinzhang Song; Mouliang Xiao; Hua Qin; Yunying Fang; Xiaokai Zhang; Tida Ge; Yu Luo; Shuokang Liu; et al. (Chemical Engineering Journal, 2025)

Designing light-guiding carriers in microalgal-bacterial systems: From optimization to integration and development perspectives - Cong-Cong Tang; Jin-Qiao Liu; Yong-Qi Cheng; Ya-Ru Hu; Zhang-Wei He; Wen-Qiong Wang; Zhi-Hua Li; Xiaochang C. Wang; Yu Tian (Chemical Engineering Journal, 2025)

Nanozeolite-coupled biochar-based phosphorus fertilizer decreases soil N2O emissions in a subtropical Moso bamboo forest - Xinyong Sun; Shuokang Liu; Caixian Tang; Jiashu Zhou; Zhenhui Jiang; Chang Dong; Yu Luo; Tida Ge; Jason C. White; Yanjiang Cai; Bing Yu; Yongfu Li (Journal of Environmental Management, 2025)

Nitrogen-induced suppression of methane uptake is alleviated by biochar in a subtropical forest soil - Jiashu Zhou; Shuokang Liu; Caixian Tang; Mouliang Xiao; Tida Ge; Yu Luo; Yanfei Dong; Bing Yu; Yanjiang Cai; Jason C. White; Yongfu Li (Environmental Research, 2025)

A novel load testing method for condition assessment of network-level highway bridges using moving artificial truck fleets in an open traffic environment - Junyong Zhou; Qingpeng Zheng; Tang Tang; Bin Wei; Xiaoyi Zhou; Colin C. Caprani (Engineering Structures, 2025)

Lead (Pb) in PM2.5 exposure hotspots and pollution sources affecting adults and children in multiple urban environments - Chien-Cheng Jung; Tzu-Ying Chiang; Yi-Jie Chung; Charles C.-K. Chou; Yi-Tang Huang; Chi-Jung Chung (Building and Environment, 2025)

Correction: Variable Toxicity by β-Blocker Class in Intentional Overdoses Reported to U.S. Poison Centers - C. James Watson; Michael C. Monuteaux; Katherine B. Tang; Michele M. Burns (Journal of Medical Toxicology, 2025)

Variable Toxicity by β-Blocker Class in Intentional Overdoses Reported To U.S. Poison Centers - C. James Watson; Michael C. Monuteaux; Katherine B. Tang; Michele M. Burns (Journal of Medical Toxicology, 2025)

Deadwood Supports Carnivores in Leaf Litter Communities in a Bark Beetle-Attacked Deadwood Simulation Experiment - N. V. Benedetto; J. J. Riggins; J. D. Tang; C. M. Siegert; J. Thomason; N. Dearing; N. A. Clay (Forest Science, 2025)

Substrate Effect on the Contribution of Ammonium and Urea to Marine Nitrification and Nitrous Oxide Production - Weiyi Tang; Catherine Hexter; Rongbo Dai; Samantha G. Fortin; John C. Tracey; Naomi Intrator; Moriah A. Kunes; Xianhui S. Wan; Amal Jayakumar; Dalin Shi; Bess B. Ward (Environmental Microbiology, 2025)
Nitrification (microbial oxidation of ammonia to nitrite and nitrate) controls nitrogen speciation and is the main source of nitrous oxide (N 2 O) in the ocean. It was recently shown that the most abundant marine ammonia oxidizers, the ammonia‐oxidising archaea (AOA), are also capable of oxidising urea, providing a previously ignored source of nitrite. Here, we show that the relative magnitude of urea and ammonia oxidation rates, and the relative rates of N 2 O production from the two substrates, is correlated with the ratio of the substrate concentrations. By examining all reported measurements of urea and ammonium concentrations and the paired urea and ammonia oxidation rates, we show that this relationship likely holds across the global ocean. Examination of newly acquired and previously published metagenomic data shows that the fraction of AOA with the genetic capability for urea oxidation increases with the urea:ammonium ratio, rather than depending on the urea or ammonium concentration alone. These results corroborate the correlation between substrate ratios and oxidation rate ratios, and extend it to N 2 O production. This may help explain the distribution of nitrification rates and N 2 O production in the ocean.

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Removal of residual antibiotics from aquaculture effluents by denitrifying woodchip bioreactors - Mathis von Ahnen; Kai Tang; Ida van de Ven; Adam C. Hambly; Henrik Rasmus Andersen; Niels Lorenzen; Per Bovbjerg Pedersen (Aquaculture, 2025)

Parvalbumin interneurons are essential for tonotopy strength in the auditory cortex - Xiaojing Tang; Zhikai Zhao; Longhui Li; Jie Tao; Yiheng Chen; Mahiber Polat; Zhiqi Yang; Zhihao Wei; Shanshan Liang; Kuan Zhang; Xiang Liao; Hongbo Jia; et al. (Science Bulletin, 2025)

Lysergic acid diethylamide inhibits status epilepticus and mortality in a mouse model of acute kainic acid-induced motor seizures - BS Rabinovitch; W Hu; C Tang; N Silverman; EC Lewis; PL Carlen (Next Research, 2025)

Elevating crop productivity and sustainability: The role of organic fertilizers in shaping wheat's nitrogen economy and photosynthetic response - Binbin Qiang; Zinan Yan; Xinbo Zhang; Mengwei Cheng; Yulin Wu; Ni Tang; Benjie C. Timbang; Tie Cai; Enke Liu; Xining Zhao; Xiaolong Ren; Xiaoli Chen (European Journal of Agronomy, 2025)

Adsorption of phosphorus on different substrates of constructed wetlands - X. Liu; M. Tang; C. Lin; H. Zhu; Z. Xu; H. Zhai; X. Tan (International Journal of Environmental Science and Technology, 2025)

Adjustment of outdoor thermal environment in a Central Business District with high-reflective material and rooftop greening - G. Huang; H. Tang; X. Li; F. Liu; J. Wang; C. Li (International Journal of Environmental Science and Technology, 2025)

The attentional boost effect: current landscape and future directions - Ricky K. C. Au; Alvin K. M. Tang (Cognitive Processing, 2025)

Probabilistic performance analysis of longitudinal tunnels based on coupled characterization of stratigraphic and geo-properties uncertainties - Chao Zhao; Wenping Gong; C. Hsein Juang; Huiming Tang; Zhongqiang Liu; Xinli Hu (Tunnelling and Underground Space Technology, 2025)

Impacts of straw addition on ryegrass (Lolium perenne L.) heavy metal absorption and microbial community structure - Jiuwei Song; Yunxiu Zhao; Yuhan Cai; Boping Tang; Fenghua Ding; Philip C. Brookes; Xingmei Liu (Plant and Soil, 2025)

Comprehensive Characterisation of the RFC1 Repeat in an Australian Cohort - Kayli C. Davies; Haloom Rafehi; Liam G. Fearnley; Penny Snell; Greta Gillies; Tess A. Field; Gábor M. Halmágyi; Kishore R. Kumar; Kate Pope; Renee Smyth; Susan E. Tomlinson; Stephen Tisch; et al. (The Cerebellum, 2025)

Unveiling fungal degradation pathways for polyurethane and polyethylene through enrichment cultures and metabolic analysis - Eyalira Jacob Okal; Jie Zhou; Yanfei Wu; Tingfang Zhong; Yue Tang; Zhengyu Sun; Ruifang Xu; Yuwei Hu; Na Hu; Jingxian Li; Samantha C. Karunarathna; Peter E. Mortimer; et al. (International Biodeterioration & Biodegradation, 2025)

Assessing Atmospheric PM2.5 as a Proxy for Subjects’ Exposure Through Seasonal, Floor, Source-Specific Analysis - Chien-Cheng Jung; Charles C.-K. Chou; Yi-Tang Huang (International Journal of Environmental Research, 2025)

Methane adsorption capacity of shale in the upper Permian Longtan Formation in the eastern Sichuan–northern Guizhou region, South China - X-M. Li; X. Tang; S-B. Guo; Y-S. Shan; E-D. Deng; C-L. Lan; B-D. Tan (Australian Journal of Earth Sciences, 2025)

Atmospheric nitrogen deposition has minor impacts on the abundance and diversity of arbuscular mycorrhizal fungi and their contribution to soil carbon stock in tropical forests - Andi Li; Peter Meidl; Senhao Wang; Bo Tang; Matthias C. Rillig; Guangcan Yu; Jing Chen; Rongzhen Liu; Zhiyang Lie; Anchi Wu; Lili Rong; Cheng Peng; et al. (Soil Biology and Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

Sustained superiority of biochar over straw for enhancing soil biological-phosphorus via the mediation of phoD-harboring bacteria in subtropical Moso bamboo forests - Zhenhui Jiang; Tony Vancov; Yunying Fang; Caixian Tang; Wenyi Zhang; Mouliang Xiao; Xinzhang Song; Jiashu Zhou; Tida Ge; Yanjiang Cai; Bing Yu; Jason C. White; et al. (Forest Ecology and Management, 2025)

Displacement reconstruction with frequency domain-invariant representation for enhancing track damage identification - Shaohua Wang; Meng Hu; Lihua Tang; Minjung Kim; Kean C. Aw (Engineering Structures, 2025)

Increased Growth Temperatures Alter Arctic Plant Responses to Heat Wave and Drought - Marta Contreras‐Serrano; Neel Lindsby; Riikka Rinnan; Emma C. N. Duegaard; Eva Rosenqvist; Shouzhi Chen; Yongshuo H. Fu; Jing Tang (Global Change Biology, 2025)
Persistent warming and higher frequency of heat waves in the Arctic are causing alterations in Arctic vegetation and plant functionality, potentially redefining the role of the Arctic ecosystem. Vegetation influences atmospheric composition through exchanges of CO 2 and volatile organic compounds (VOCs), both processes exhibiting a strong response to temperature variations. However, our quantitative understanding of how increased temperatures interact with extreme weather events, namely heat waves and drought, to affect Arctic plant processes remains limited. Here, we measure phenology, photosynthesis, leaf fluorescence and VOC emissions from three widely distributed Arctic shrubs, Betula nana , Empetrum hermaphroditum and Salix spp., in response to future climate. We use state‐of‐the‐art climate chambers to test the effects of warmer growth temperatures on Arctic shrub responses to heat waves and drought. Our results show that increased growth temperatures advance leaf unfolding by 24 days in B. nana and 17 days in E. hermaphroditum , and increase VOC emissions across species. For B. nana , photosynthesis decreased by 42% during the heat wave and by 72% during drought. In contrast, Salix spp. and E. hermaphroditum experienced decreased photosynthesis only during drought, by 62% and 71%, respectively. The VOC emissions during the heat wave shifted toward a less diverse compound profile: acetaldehyde emissions increased for both control and warmed plants in all species, and isoprene emissions increased in Salix spp. Additionally, plants grown at higher temperatures exhibited a twofold increase in emissions compared to control plants during the heat wave, suggesting a higher temperature sensitivity of emissions. Our study indicates that warming and increasingly frequent extreme weather events will significantly impact Arctic plant phenology, photosynthesis and the diversity and rates of VOCs emitted into the atmosphere, contributing to modifying the regional climate.

Difference analysis of organic matter-mediated heavy metal pollution in the sediments of urban water bodies - Wenzhong Tang; Liu Sun; Yufeng Zhu; Jack C. Ng; Jianyin Huang; Zuben Xu; Hong Zhang (Science of The Total Environment, 2025)

A trimaran structure damage identification method based on machine learning - Haoyun Tang; Deyuan Ren; Baiqiao Chen; C. Guedes Soares (Ocean Engineering, 2025)

From soil health to agricultural productivity: The critical role of soil constraint management - Tong Li; Lizhen Cui; Vilim Filipović; Caixian Tang; Yunru Lai; Bernhard Wehr; Xiufang Song; Scott Chapman; Hongdou Liu; Ram C. Dalal; Yash P. Dang (CATENA, 2025)

The dissimilarity between multiple management practices drives the impact on soil properties and functions - Huiying Li; Bo Tang; Anika Lehmann; Rebecca Rongstock; Yanjie Zhu; Matthias C. Rillig (Soil Ecology Letters, 2025)
Higher dissimilarity between restoration factors boosted soil microbial activities when multiple factors jointly applied. More diverse management practices enhanced soil aggregate stability and improved soil pH. Increasing restoration factors up to 8 factors only influenced soil properties (water stable aggregates and soil pH) but not soil microbial activities. A range of land management practices are available to achieve better soil quality, but their combined effects remain understudied. We hypothesize that more diverse management practices, meaning higher dissimilarity, lead to stronger effects on soil functions and properties. Eight practices (biochar, compost, clay, amorphous silica, basalt, microbial inoculum, reduced physical disturbance and organic matter diversity) were selected with 20 replicates for treatments involving 2, 4, or 6 factors and 10 replicates for 8 factor treatments. We investigated the impact of individual factors, factor number, factor dissimilarity and factor composition on soil respiration, soil enzymatic activities (β-glucosidase, β-D-cellobiosidase, β-N-acetylglucosaminidase and phosphatase), soil pH, water stable aggregates and permanganate oxidizable carbon fraction. By including dissimilarity in addition to factor number, variance explained for soil respiration and enzymatic activities increased up to 54.21%. For soil pH and water-stable aggregates, explained variability increased to 65.57% and 57.38%, respectively. More diverse management practices boosted soil microbial activities, enhanced soil aggregate stability, improved soil pH while reducing labile carbon, whereas factor number only influenced water stable aggregates and soil pH. Our study highlights the importance of management practices diversity in soil functions and properties and calls for further research on synergistic combinations of diverse interventions.

Timescale Matters: Finer Temporal Resolution Influences Driver Contributions to Global Soil Respiration - Benjamin Laffitte; Tao Zhou; Zhihan Yang; Philippe Ciais; Jinshi Jian; Ni Huang; Barnabas C. Seyler; Xiangjun Pei; Xiaolu Tang (Global Change Biology, 2025)
Understanding the dynamics of soil respiration ( R s ) and its environmental drivers is crucial for accurately modeling terrestrial carbon fluxes. However, current methodologies often lead to divergent estimates and rely on annual predictions that may overlook critical interactions occurring at seasonal scales. A critical knowledge gap lies in understanding how temporal resolution affects both R s predictions and their environmental drivers. Here, we employ deep learning models to predict global R s at monthly (MRM) and annual (ARM) scales from 1982 to 2018. We then consider three main drivers potentially affecting R s , including temperature, precipitation, and a vegetation proxy (leaf area index; LAI). Our models demonstrate strong predictive capabilities with global R s estimation of 79.4 ± 5.7 Pg C year −1 for the MRM and 78.3 ± 7.5 Pg C year −1 for ARM (mean ± SD). While the difference in global estimations between both models is small, there are notable disparities in the spatial contribution of dominant drivers. The MRM highlights an influence of both temperature and LAI, while the ARM emphasizes a dominant role of precipitation. These findings underscore the critical role of temporal resolution in capturing seasonal variations and identifying key R s ‐environment relationships that annual models may obscure. High temporal resolution R s predictions, such as those provided by the MRM, are essential for capturing nuanced seasonal interactions between R s and its drivers, refining carbon flux models, detecting critical seasonal thresholds, and enhancing the reliability of future Earth system predictions. This work highlights the need for further research into monthly and seasonal R s variations, as well as higher timescale resolutions, to advance our understanding of ecosystem carbon dynamics in a rapidly changing climate.

Development of a PBPK Model for Lamotrigine which Incorporates Metabolism by UGT2B10: Impact of UGT2B10 Poor Metabolizer Phenotype and Pregnancy - Iain Gardner; Aki T. Heikkinen; Lloyd Wei Tat Tang; Kimberly Lapham; Theunis C. Goosen (The AAPS Journal, 2025)

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Spatio-temporal tectonic progression in the Dharwar Craton: Insights from volcanic records of Archean greenstone belts - G. Harshitha; Jayant K Yadav; C. Manikyamba; M. Santosh; Li Tang; K.S.V. Subramanyam (Precambrian Research, 2025)

Freezing-Driven Crack Initiation and Propagation in Hard Rock - Tingting Wang; Charlie C. Li; Natalie Bennett; Chun’an Tang (Rock Mechanics and Rock Engineering, 2025)

Highly efficient synthetic bacterial consortium for biodegradation of aromatic volatile organic compounds: Behavior and mechanism - Ying Lv; Xingyu Liu; Bowei Chen; Mingjiang Zhang; Chuiyun Tang; Tian C. Zhang (Bioresource Technology, 2025)

Quantifying the effects of the microphysical hygroscopic restructuring of soot on ensemble optical properties and satellite aerosol optical depth retrievals - Kuo-En Chang; Tang-Huang Lin; Ta-Chih Hsiao; Yi-Ling Chang; Tzu-Chi Lin; Chih-Yu Chan; Charles C.-K. Chou (Science of The Total Environment, 2024)

Carbonate δ13C chemostratigraphy of the Hunjiang Group in North China and a tentative stratigraphic framework for the Meso-Neoproterozoic transition - Junyao Kang; Qing Tang; Benjamin C. Gill; Rachel Reid; Wentao Zheng; Shuhai Xiao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Lung cell injury risks of PM2.5 exposure in the high humidity and low solar radiation environment of southwestern China - Qin Zhang; Xuan Li; Xiaomeng Li; Ronghua Zhang; Bi Ren; Hanxiong Che; Xin Qi; Jiawei Zhou; Jiancai Tang; Andre S.H. Prevot; Zhenzhong Liu; Li Jiang; et al. (Atmospheric Environment, 2024)

PGC1-α in diabetic kidney disease: unraveling renoprotection and molecular mechanisms - Siyang Ye; Meng Zhang; Sydney C. W. Tang; Bin Li; Wei Chen (Molecular Biology Reports, 2024)

Training with reduced carbohydrate availability affects markers of bone resorption and formation in male academy soccer players from the English Premier League - Reuben Stables; Liam Anderson; Craig Sale; Marcus P. Hannon; Rachel Dunn; Jonathan C. Y. Tang; William D. Fraser; Nessan B. Costello; Graeme L. Close; James P. Morton (European Journal of Applied Physiology, 2024)
Purpose To test the hypothesis that training with reduced carbohydrate (CHO) availability increases bone resorption in adolescent soccer players. Methods In a randomised crossover design, ten male players (age: 17.4 ± 0.8 years) from an English Premier League academy completed an acute 90-min field-based training session (occurring between 10:30–12:00) in conditions of high (TRAIN HIGH; 1.5 g.kg −1 , 60 g, 1.5 g.kg −1 and 1.5 g.kg −1 consumed at 08:00, during training, 12:30 and 13:30, respectively) or low CHO availability (TRAIN LOW; 0 g.kg −1 ). Participants also completed a non-exercise trial (REST) under identical dietary conditions to TRAIN LOW. Venous blood samples were obtained at 08:30, 10:30, 12:30 and 14:30 for assessment of bone resorption (βCTX), bone formation (PINP) and calcium metabolism (PTH and ACa). Results External training load did not differ (all P > 0.05) between TRAIN HIGH and TRAIN LOW, as evident for total distance (5.6 ± 0.8; 5.5 ± 0.1 km), average speed (81 ± 9; 85 ± 12 m.min −1 ) and high-speed running (350 ± 239; 270 ± 89 m). Area under the curve for both βCTX and PINP was significantly greater ( P < 0.01 and P = 0.03) in TRAIN LOW versus TRAIN HIGH, whilst no differences in PTH or ACa ( P = 0.11 and P = 0.89) were observed between all three trials. Conclusion CHO restriction before, during and after an acute soccer training session increased bone (re)modelling markers in academy players. Despite acute anabolic effects of bone formation, the long-term consequence of bone resorption may impair skeletal development and increase injury risk during growth and maturation.

A Comparison Between the Gaseous and Particulate Emissions from Diesel and Natural Gas Yard Tractors - Tianbo Tang; Hanwei Zhu; Tianyi Ma; Peng Hao; Thomas D. Durbin; Kent C. Johnson; Georgios Karavalakis (Emission Control Science and Technology, 2024)

Plasma proteomic signature of risk and prognosis of frailty in the UK Biobank - Jianhong Xu; Jingyun Liu; Junhan Tang; Jinhui Liao; Xiaojuan Liu; Michelle C. Odden; Chenkai Wu (GeroScience, 2024)

Atmospheric pressure dielectric barrier discharge plasma for in-situ water treatment using a bubbling reactor - Xin Tang; Antônio D.N. Ferraz Júnior; Kersti Karu; Luiza C. Campos; Minkwan Kim (Journal of Environmental Management, 2024)

Restoring functional integrity of the global production ecosystem through biological control - Kris A.G. Wyckhuys; Baogen Gu; Ibtissem Ben Fekih; Robert Finger; Mark Kenis; Yanhui Lu; Sevgan Subramanian; Fiona H.M. Tang; Donald C. Weber; Wei Zhang; Buyung A.R. Hadi (Journal of Environmental Management, 2024)

Displacement prediction of landslides at slope-scale: Review of physics-based and data-driven approaches - Wenping Gong; Shaoyan Zhang; C. Hsein Juang; Huiming Tang; Shiva P. Pudasaini (Earth-Science Reviews, 2024)

A review of rapid food safety testing: using lateral flow assay platform to detect foodborne pathogens - Nadin Younes; Hadi M. Yassine; Katerina Kourentzi; Patrick Tang; Dmitri Litvinov; Richard C. Willson; Laith J. Abu-Raddad; Gheyath K. Nasrallah (Critical Reviews in Food Science and Nutrition, 2024)

Bioprocesses for lactic acid production from organic wastes toward industrialization-a critical review - Jialing Tang; Zongkun Hu; Yunhui Pu; Xiaochang C. Wang; Abdelfatah Abomohra (Journal of Environmental Management, 2024)

Promoting symbiotic relationship between microalgae and bacteria in wastewater treatment processes: Technic comparison, microbial analysis, and future perspectives - Cong-Cong Tang; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2024)

Monacolin-K loaded MIL-100(Fe) metal–organic framework induces ferroptosis on metastatic triple-negative breast cancer - Chien-Hui Yu; Glemarie C. Hermosa; An-Cheng Sun; Chia-Wen Kevin Wu; Mi-Tang Gao; Chun Wu; Hui-Min David Wang (Chemical Engineering Journal, 2024)

Discovery of a novel marine bacterial AIEgen that lights up specific G-quadruplexes - Wenkang Ye; Xinnan Wang; Parvej Alam; Changdong Liu; Monica C. Suen; Jianwei Tang; Herman H.Y. Sung; Ian D. Williams; Eric Y. Yu; Jacky W.Y. Lam; Guang Zhu; Ben-Zhong Tang; et al. (Chemical Engineering Journal, 2024)

Seasonally Changing Interactions of Species Traits of Termites and Trees Promote Complementarity in Coarse Wood Decomposition - Chao Guo; Bin Tuo; Sebastian Seibold; Hang Ci; Bi‐Le Sai; Han‐Tang Qin; En‐Rong Yan; Johannes H. C. Cornelissen (Ecology Letters, 2024)
Complementary resource use by functionally different species may accelerate ecosystem processes. However, how co‐variation in plant traits and animal traits promotes complementarity through temporal plant–animal interactions is poorly understood, even less so in detrital systems, thereby hampering our fundamental understanding of decomposition and carbon turnover. We hypothesised that, in seasonal subtropical forests where termites are major deadwood decomposers, trait complementarity of both termite species and tree species should promote overall deadwood decomposition through different seasons and years. Findings from a four‐year coarse wood decomposition experiment involving 27 tree and 5 termite species support this hypothesis. Phenological and mandibular traits of the two most abundant termite species controlled wood decomposition of tree species differing in wood traits, through the seasons over 4 years, thereby promoting overall deadwood decomposition rates. Our findings indicate that complementarity in functional trait co‐variation in plants and animals plays an important role in carbon cycling.

UGT2B10 is the Major UDP-Glucuronosyltransferase 2B Isoform Involved in the Metabolism of Lamotrigine and is Implicated in the Drug-Drug Interaction with Valproic Acid - Lloyd Wei Tat Tang; Kimberly Lapham; Theunis C. Goosen (The AAPS Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Maize straw increases while its biochar decreases native organic carbon mineralization in a subtropical forest soil - Jiashu Zhou; Shaobo Zhang; Junyan Lv; Caixian Tang; Haibo Zhang; Yunying Fang; Ehsan Tavakkoli; Tida Ge; Yu Luo; Yanjiang Cai; Bing Yu; Jason C. White; et al. (Science of The Total Environment, 2024)

Coupling physiochemical adsorption with biodegradation for enhanced removal of microcystin-LR in water - Shengyin Tang; Lixun Zhang; Haoxin Zhu; Sunny C. Jiang (Science of The Total Environment, 2024)

Understanding predictors of mistletoe infection across an urban university campus in Southwest China - Yuchen Niu; Benjamin Laffitte; Sophia Zuoqiu; Barnabas C. Seyler; Zhengang Ha; Jianan Chen; Lei Chen; Ya Tang (Urban Ecosystems, 2024)
Due to the importance of trees in urban ecosystems, it is crucial to understand the distribution, prevalence, and intensity of parasitic mistletoe infection across urban landscapes. In this study, we aimed to understand how various tree-related factors (e.g., tree taxonomy, size, pruning history, nativity, foliage, density, and diversity) might influence mistletoe prevalence and infection intensity across a typical subtropical urban greenspace. We surveyed 6,012 trees representing 96 species, 76 genera, and 44 families across a large, urban university campus in a major Southwest Chinese city. In total, we found 353 mistletoe host trees (prevalence: 5.87%), largely concentrated on the eastern part of campus, partially due to the proximity of waterbodies and a large adjacent greenspace, as well as higher tree density. To understand how predictors affected the prevalence and intensity of mistletoe infection, we used a hurdle model fitting our zero-inflated count data. Four independent variables significantly affected the prevalence of mistletoe infestation, with three demonstrating positive correlations (crown width, tree density, and tree diversity). One variable (evergreen foliage) negatively correlated with mistletoe prevalence. However, only one factor was found to significantly affect mistletoe infection intensity (crown width, positively). Due to the variety of ecosystem services mistletoes provide, more studies are necessary to assess the impact of various mistletoe management strategies, especially on urban biodiversity.

The genomic and immunogenomic landscape of mechanics pathway informs clinical prognosis and response to mechanotherapy - Peidong Zhang; Peiwei Li; Muya Tang; Ryan C. Gimple; Liang Huang; Jing Yue; Qiuhong Shen; Yiwei Du; Qian Zhang; Zhengnan Yang; Haihuai He; Kailin Yang; et al. (Science China Life Sciences, 2024)

Sustainable regulation of calcium magnesium phosphate and rapeseed cake on soil-tea system in Mount Lushan, China - C. Han; Y. Ding; Z. J. Tang; Y. Q. Lai; M. Liu (Environmental Geochemistry and Health, 2024)

Children's exposure to brominated flame retardants in the home: The TESIE study - Kate Hoffman; Xuening Tang; Ellen M. Cooper; Stephanie C. Hammel; Andreas Sjodin; Allison L. Phillips; Thomas F. Webster; Heather M. Stapleton (Environmental Pollution, 2024)

Probabilistic analysis of lateral behaviour of offshore wind turbine monopile considering uncertainties of geological model and loads - Chao Zhao; Wenping Gong; C. Hsein Juang; Huiming Tang; Xinli Hu; Zhengwei Li (Computers and Geotechnics, 2024)

Degradation of hydroxypropyl guar gum by dual oxidant system catalyzed by hydrotalcite supported zero-valent transition metal - B. Bai; Q. Liu; T. Li; R. Zhou; C. Qu; Y. Tang (International Journal of Environmental Science and Technology, 2024)

Arbuscular mycorrhizal fungi attenuate negative impact of drought on soil functions - Bo Tang; Jing Man; Anika Lehmann; Matthias C. Rillig (Global Change Biology, 2024)
Although positive effects of arbuscular mycorrhizal (AM) fungi on plant performance under drought have been well documented, how AM fungi regulate soil functions and multifunctionality requires further investigation. In this study, we first performed a meta‐analysis to test the potential role of AM fungi in maintaining soil functions under drought. Then, we conducted a greenhouse experiment, using a pair of hyphal ingrowth cores to spatially separate the growth of AM fungal hyphae and plant roots, to further investigate the effects of AM fungi on soil multifunctionality and its resistance against drought. Our meta‐analysis showed that AM fungi promote multiple soil functions, including soil aggregation, microbial biomass and activities of soil enzymes related to nutrient cycling. The greenhouse experiment further demonstrated that AM fungi attenuate the negative impact of drought on these soil functions and thus multifunctionality, therefore, increasing their resistance against drought. Moreover, this buffering effect of AM fungi persists across different frequencies of water supply and plant species. These findings highlight the unique role of AM fungi in maintaining multiple soil functions by mitigating the negative impact of drought. Our study highlights the importance of AM fungi as a nature‐based solution to sustaining multiple soil functions in a world where drought events are intensifying.

Mycorrhization enhances plant growth and stabilizes biomass allocation under drought - Bo Tang; Jing Man; Ferran Romero; Joana Bergmann; Anika Lehmann; Matthias C. Rillig (Global Change Biology, 2024)
Plants and their symbionts, such as arbuscular mycorrhizal (AM) fungi, are increasingly subjected to various environmental stressors due to climate change, including drought. As a response to drought, plants generally allocate more biomass to roots over shoots, thereby facilitating water uptake. However, whether this biomass allocation shift is modulated by AM fungi remains unknown. Based on 5691 paired observations from 154 plant species, we conducted a meta‐analysis to evaluate how AM fungi modulate the responses of plant growth and biomass allocation (e.g., root‐to‐shoot ratio, R/S) to drought. We found that AM fungi attenuate the negative impact of drought on plant growth, including biomass production, photosynthetic performance and resource (e.g. nutrient and water) uptake. Accordingly, drought significantly increased R/S in non‐inoculated plants, but not in plants symbiotic with established AM fungal symbioses. These results suggest that AM fungi promote plant growth and stabilize their R/S through facilitating nutrient and water uptake in plants under drought. Our findings highlight the crucial role of AM fungi in enhancing plant resilience to drought by optimizing resource allocation. This knowledge opens avenues for sustainable agricultural practices that leverage symbiotic relationships for climate adaptation.

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Wildfire smoke impacts lake ecosystems - Mary Jade Farruggia; Janice Brahney; Andrew J. Tanentzap; Jennifer A. Brentrup; Ludmila S. Brighenti; Sudeep Chandra; Alicia Cortés; Rocio L. Fernandez; Janet M. Fischer; Alexander L. Forrest; Yufang Jin; Kenneth Larrieu; et al. (Global Change Biology, 2024)
Wildfire activity is increasing globally. The resulting smoke plumes can travel hundreds to thousands of kilometers, reflecting or scattering sunlight and depositing particles within ecosystems. Several key physical, chemical, and biological processes in lakes are controlled by factors affected by smoke. The spatial and temporal scales of lake exposure to smoke are extensive and under‐recognized. We introduce the concept of the lake smoke‐day, or the number of days any given lake is exposed to smoke in any given fire season, and quantify the total lake smoke‐day exposure in North America from 2019 to 2021. Because smoke can be transported at continental to intercontinental scales, even regions that may not typically experience direct burning of landscapes by wildfire are at risk of smoke exposure. We found that 99.3% of North America was covered by smoke, affecting a total of 1,333,687 lakes ≥10 ha. An incredible 98.9% of lakes experienced at least 10 smoke‐days a year, with 89.6% of lakes receiving over 30 lake smoke‐days, and lakes in some regions experiencing up to 4 months of cumulative smoke‐days. Herein we review the mechanisms through which smoke and ash can affect lakes by altering the amount and spectral composition of incoming solar radiation and depositing carbon, nutrients, or toxic compounds that could alter chemical conditions and impact biota. We develop a conceptual framework that synthesizes known and theoretical impacts of smoke on lakes to guide future research. Finally, we identify emerging research priorities that can help us better understand how lakes will be affected by smoke as wildfire activity increases due to climate change and other anthropogenic activities.

Plant-based milk: unravel the changes of the antioxidant index during processing and storage – a review - S. C. Tong; L. F. Siow; T. K. Tang; Y. Y. Lee (Critical Reviews in Food Science and Nutrition, 2024)

Role of phosphate in microalgal-bacterial symbiosis system treating wastewater containing heavy metals - Cong-Cong Tang; Ya-Ru Hu; Min Zhang; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2024)

The natural history and genotype–phenotype correlations of TMPRSS3 hearing loss: an international, multi-center, cohort analysis - Brett M. Colbert; Cris Lanting; Molly Smeal; Susan Blanton; Derek M. Dykxhoorn; Pei-Ciao Tang; Richard L. Getchell; Hedwig Velde; Mirthe Fehrmann; Ryan Thorpe; Prem Chapagain; Heidy Elkhaligy; et al. (Human Genetics, 2024)
TMPRSS3 -related hearing loss presents challenges in correlating genotypic variants with clinical phenotypes due to the small sample sizes of previous studies. We conducted a cross-sectional genomics study coupled with retrospective clinical phenotype analysis on 127 individuals. These individuals were from 16 academic medical centers across 6 countries. Key findings revealed 47 unique TMPRSS3 variants with significant differences in hearing thresholds between those with missense variants versus those with loss-of-function genotypes. The hearing loss progression rate for the DFNB8 subtype was 0.3 dB/year. Post-cochlear implantation, an average word recognition score of 76% was observed. Of the 51 individuals with two missense variants, 10 had DFNB10 with profound hearing loss. These 10 all had at least one of 4 TMPRSS3 variants predicted by computational modeling to be damaging to TMPRSS3 structure and function. To our knowledge, this is the largest study of TMPRSS3 genotype–phenotype correlations. We find significant differences in hearing thresholds, hearing loss progression, and age of presentation, by TMPRSS3 genotype and protein domain affected. Most individuals with TMPRSS3 variants perform well on speech recognition tests after cochlear implant, however increased age at implant is associated with worse outcomes. These findings provide insight for genetic counseling and the on-going design of novel therapeutic approaches.

Pyrogenic organic matter decreases while fresh organic matter increases soil heterotrophic respiration through modifying microbial activity in a subtropical forest - Jiashu Zhou; Shaobo Zhang; Dafeng Hui; Tony Vancov; Yunying Fang; Caixian Tang; Zhenhui Jiang; Tida Ge; Yanjiang Cai; Bing Yu; Jason C. White; Yongfu Li (Biology and Fertility of Soils, 2024)

Characterization and Applications of Permeabilized Hepatocytes in Drug Discovery - Sam Zhang; Christine C. Orozco; Lloyd Wei Tat Tang; Jillian Racich; Anthony A. Carlo; George Chang; David Tess; Christopher Keefer; Li Di (The AAPS Journal, 2024)

Deciphering the synergistic effects of photolysis and biofiltration to actuate elimination of estrogens in natural water matrix - Fan Huang; Junwang Tang; Like Xu; Luiza C. Campos (Water Research, 2024)

Transplanted Ginkgo growth rates indicate common Chinese nursery techniques may severely limit urban ecosystem services - Benjamin Laffitte; Barnabas C. Seyler; Xuexin Yang; Ya Tang (Science of The Total Environment, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

A Highly Efficient and Energy Saving Electrochromic Platform for Adaptive Visible and Near-Infrared Light Modulation - Dajiang Tang; Junxin Wang; Xiaoyu Huang; Dashui Zhang; Sheng Cao; Linfei Yin; Zhangfa Tong; Hongbing Ji; Rachel C. Evans; Hui-Ying Qu (Chemical Engineering Journal, 2024)

Phosphonate functionalized magnetic mesoporous silica for rare earth element recovery from citrate assisted solid waste extracts - Dien Li; Yinghao Wen; Lei Hu; Xiaoyu Xu; Breann S. Spencer; Shani Egodawatte; Sarah C. Larsen; Yuanzhi Tang (Applied Geochemistry, 2024)

In-use NOx and black carbon emissions from heavy-duty freight diesel vehicles and near-zero emissions natural gas vehicles in California's San Joaquin Air Basin - Tianyi Ma; Chengguo Li; Ji Luo; Chas Frederickson; Tianbo Tang; Thomas D. Durbin; Kent C. Johnson; Georgios Karavalakis (Science of The Total Environment, 2024)

A comparative study of air pollution tolerance capabilities of four tree species in Xi’an city, China - J. Zheng; X. Qu; R. Hou; X. Tang; Z. Xu; Z. Huang; Z. Wang; W. Zhang; C. Yang; T. Li (International Journal of Environmental Science and Technology, 2024)

Investigating the association between a history of depression and biomarkers of Alzheimer’s disease, cerebrovascular disease, and neurodegeneration in patients with dementia - Patrick Salwierz; Simrika Thapa; Foad Taghdiri; Anna Vasilevskaya; Chloe Anastassiadis; David F. Tang-Wai; Angela C. Golas; M. Carmela Tartaglia (GeroScience, 2023)

Advances, challenges, and prospects in microalgal-bacterial symbiosis system treating heavy metal wastewater - Xing-Rui Zhou; Rong Wang; Cong-Cong Tang; Cristiano Varrone; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Chemosphere, 2023)

Detection and attribution of an anomaly in terrestrial photosynthesis in Europe during the COVID-19 lockdown - Angela Che Ing Tang; Christophe R. Flechard; Nicola Arriga; Dario Papale; Paul C. Stoy; Nina Buchmann; Matthias Cuntz; John Douros; Silvano Fares; Alexander Knohl; Ladislav Šigut; Guillaume Simioni; et al. (Science of The Total Environment, 2023)

Alteration of microbial carbon and nitrogen metabolism within the soil metagenome with grazing intensity at semiarid steppe - Zhen Wang; Kai Tang; Paul C. Struik; Muhammad Nadeem Ashraf; Tongrui Zhang; Yanning Zhao; Riliga Wu; Ke Jin; Yuanheng Li (Journal of Environmental Management, 2023)

Correction to: Endogenous Neural Stem Cell–induced Neurogenesis after Ischemic Stroke: Processes for Brain Repair and Perspectives - Hailiang Tang; Yao Li; Weijun Tang; Jianhong Zhu; Graham C. Parker; John H. Zhang (Translational Stroke Research, 2023)

Investigation of the Artificial Saliva and Saline Droplet Size Measurement Accuracy for COVID-19 Infection Control - Thomas Y. Wu; Yi-Hung Liu; Fang-hsin Lin; Yue Liu; Junjie Liu; Jinsang Jung; Wesley Zongrong Yu; Qinde Liu; Richard Y. C. Shin; Tang Lin Teo (Aerosol Science and Engineering, 2023)

Arbuscular mycorrhizal fungi benefit plants in response to major global change factors - Bo Tang; Jing Man; Anika Lehmann; Matthias C. Rillig (Ecology Letters, 2023)
Land plants play a key role in global carbon cycling, but the potential role of arbuscular mycorrhizal fungi (AMF) in the responses of a wide range of plant species to global change factors (GCFs) remains limited. Based on 1100 paired observations from 181 plant species, we conducted a meta‐analysis to test the role of AMF in plant responses to four GCFs: drought, warming, nitrogen (N) addition and elevated CO 2 . We show that AMF significantly ameliorate the negative effects of drought on plant performance. The GCFs N addition and elevated CO 2 significantly enhance the performance of AM plants but not of non‐inoculated plants. AM plants show better performance than their non‐inoculated counterparts under warming, although neither of them showed a significant response to this GCF. These results suggest that AMF benefit plants in response to GCFs. Our study highlights the importance of AMF in enhancing plant performance under ongoing global change.

Bioenergy production from swine wastewater based on a combined process of anaerobic dynamic membrane reactor and microalgae cultivation: Feasibility and performance - Jialing Tang; Hao Yang; Yunhui Pu; Yisong Hu; Xiangjiang Qu; Si Chen; Xiaochang C. Wang; Huu Hao Ngo; Yuyou Li; Abdelfatah Abomohra (Science of The Total Environment, 2023)

An investigation of grain characteristics, dough quality and baking performance of perennial wheats from contrasting parentage - Denise Pleming; Matthew Newell; Richard C. Hayes; Ke Hong Tang; Beth Penrose; Matthew Wilson; Annie Riaz; Chris Blanchard (Journal of Cereal Science, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Estimated mangrove carbon stocks and fluxes to inform MRV for REDD+ using a process-based model - Zhaohua Dai; Carl C. Trettin; Andrew J. Burton; Wenwu Tang; Mwita M. Mangora (Estuarine, Coastal and Shelf Science, 2023)

Caproic acid production from food waste using indigenous microbiota: Performance and mechanisms - Jialing Tang; Hao Yang; Yunhui Pu; Yisong Hu; Jin Huang; Ni Jin; Xinrui He; Xiaochang C. Wang (Bioresource Technology, 2023)

Expanding the ethanol blend wall in California: Emissions comparison between E10 and E15 - Tianbo Tang; Cavan McCaffery; Tianyi Ma; Peng Hao; Thomas D. Durbin; Kent C. Johnson; Georgios Karavalakis (Fuel, 2023)

Energy storage properties of samarium-doped bismuth sodium titanate-based lead-free ceramics - Xuyao Tang; Zimeng Hu; Vladimir Koval; Bin Yang; Graham C. Smith; Haixue Yan (Chemical Engineering Journal, 2023)

Insights into roles of triclosan in microalgal–bacterial symbiosis system treating wastewater - Cong-Cong Tang; Tian-Yang Wang; Rong Wang; Cristiano Varrone; Zixuan Gan; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Bioresource Technology, 2023)

Using tree rings to detect a CO2 fertilization effect: a global review - Benjamin Laffitte; Barnabas C. Seyler; Pengbo Li; Zhengang Ha; Ya Tang (Trees, 2023)

Numerical simulation of turbidity currents using consistent particle method - X.-Q. Tang; C. G. Koh; M. Luo (Advances in Water Resources, 2023)

S17-02: The Long-term Impact of Perinatal Exposures on Susceptibility to Immune-mediated Diseases - K.A. Rychlik; E.J. Illingworth; S.E. Attreed; S.S. Sanchez; A. Grant-Alfieri; M.C. Rodriguez Steube; A. Mathur; I.F. Sanchez; C. Tang; M. Suresh; G. Lopez-Cecetaite; P. Sadhukhan; et al. (Toxicology Letters, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Integrated ground and vertical measurement techniques to characterize overhead atmosphere: Case studies of local versus transboundary pollution - Chang-Feng Ou-Yang; Chih-Chung Chang; Sheng-Hsiang Wang; Charles C.-K. Chou; Ming-Tung Chuang; Tang-Huang Lin; Wei-Nai Chen; Ta-Chih Hsiao; Ming-Cheng Yen; Yueh-Chen Wang; Neng-Huei Lin; Jia-Lin Wang (Science of The Total Environment, 2023)

A scalable framework for quantifying field-level agricultural carbon outcomes - Kaiyu Guan; Zhenong Jin; Bin Peng; Jinyun Tang; Evan H. DeLucia; Paul C. West; Chongya Jiang; Sheng Wang; Taegon Kim; Wang Zhou; Tim Griffis; Licheng Liu; et al. (Earth-Science Reviews, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

Multi-elements characteristic and potential risk of heavy metals in MOUTAN CORTEX from Anhui Province, China - X. Xue; G. Liu; Q. Tang; H. Shi; D. Wu; C. Jin; H. Zhao; Y. Wei; Y. Zhang (International Journal of Environmental Science and Technology, 2023)

Flexible preparation of nanoporous SiO2 aerogel as novel adsorbent for efficient adsorption of Zearalenone - Tang Ruihao; Wang Huihao; Chen Yadong; C. Srinivasakannan; Duan Xinhui; Wang Xin (Journal of Environmental Chemical Engineering, 2023)

Endogenous Neural Stem Cell–induced Neurogenesis after Ischemic Stroke: Processes for Brain Repair and Perspectives - Hailiang Tang; Yao Li; Weijun Tang; Jianhong Zhu; Graham C. Parker; John H. Zhang (Translational Stroke Research, 2023)

Identification and genome sequencing of an influenza H3N2 variant in wastewater from elementary schools during a surge of influenza A cases in Las Vegas, Nevada - Van Vo; Anthony Harrington; Ching-Lan Chang; Hayley Baker; Michael A. Moshi; Nabih Ghani; Jose Yani Itorralba; Richard L. Tillett; Elizabeth Dahlmann; Natnael Basazinew; Richard Gu; Tiffany D. Familara; et al. (Science of The Total Environment, 2023)

Optimization of site exploration program based on coupled characterization of stratigraphic and geo-properties uncertainties - Chao Zhao; Wenping Gong; C. Hsein Juang; Huiming Tang; Xinli Hu; Lei Wang (Engineering Geology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Embedded information of aerosol type, hygroscopicity and scattering enhancement factor revealed by the relationship between PM2.5 and aerosol optical depth - Kuo-En Chang; Ta-Chih Hsiao; Si-Chee Tsay; Tang-Huang Lin; Stephen M. Griffith; Chian-Yi Liu; Charles C.-K. Chou (Science of The Total Environment, 2023)

A comparative study of self-centering precast concrete walls with replaceable buckling-restrained yielding plates or friction dissipation components - Xinghua Li; Yahya C. Kurama; Gang Wu; Haoran Cui; Yuchuan Tang; Yihua Zeng (Engineering Structures, 2023)

Nitrogen increases soil organic carbon accrual and alters its functionality - Bo Tang; Katherine S. Rocci; Anika Lehmann; Matthias C. Rillig (Global Change Biology, 2023)
Nitrogen (N) availability has been considered as a critical factor for the cycling and storage of soil organic carbon (SOC), but effects of N enrichment on the SOC pool appear highly variable. Given the complex nature of the SOC pool, recent frameworks suggest that separating this pool into different functional components, for example, particulate organic carbon (POC) and mineral‐associated organic carbon (MAOC), is of great importance for understanding and predicting SOC dynamics. Importantly, little is known about how these N‐induced changes in SOC components (e.g., changes in the ratios among these fractions) would affect the functionality of the SOC pool, given the differences in nutrient density, resistance to disturbance, and turnover time between POC and MAOC pool. Here, we conducted a global meta‐analysis of 803 paired observations from 98 published studies to assess the effect of N addition on these SOC components, and the ratios among these fractions. We found that N addition, on average, significantly increased POC and MAOC pools by 16.4% and 3.7%, respectively. In contrast, both the ratios of MAOC to SOC and MAOC to POC were remarkably decreased by N enrichment (4.1% and 10.1%, respectively). Increases in the POC pool were positively correlated with changes in aboveground plant biomass and with hydrolytic enzymes. However, the positive responses of MAOC to N enrichment were correlated with increases in microbial biomass. Our results suggest that although reactive N deposition could facilitate soil C sequestration to some extent, it might decrease the nutrient density, turnover time, and resistance to disturbance of the SOC pool. Our study provides mechanistic insights into the effects of N enrichment on the SOC pool and its functionality at global scale, which is pivotal for understanding soil C dynamics especially in future scenarios with more frequent and severe perturbations.

A study to characterize the lead isotopic fingerprint in PM2.5 emitted from incense stick and cigarette burning - Chien-Cheng Jung; Zih-Hong Syu; Charles C.-K. Chou; Yi-Tang Huang (Environmental Science and Pollution Research, 2023)

Rapid, sensitive detection of PFOA with smartphone-based flow rate analysis utilizing competitive molecular interactions during capillary action - Lane E. Breshears; Samantha Mata-Robles; Yisha Tang; Jacob C. Baker; Kelly A. Reynolds; Jeong-Yeol Yoon (Journal of Hazardous Materials, 2023)

Evolution of diagenetic fluids in the deeply buried, upper Ediacaran Dengying Formation, Central Sichuan Basin, China - Y. J. Hu; C. F. Cai; Y. Li; R. Zhou; Y. J. Tang; J. F. Hu; F. C. Lu; P. Sun (Australian Journal of Earth Sciences, 2023)

Higher resistance and resilience of bacterial growth to drought in grasslands with historically lower precipitation - Yuqian Tang; Sara Winterfeldt; Albert C. Brangarí; Lettice C. Hicks; Johannes Rousk (Soil Biology and Biochemistry, 2023)

Role of carboxysomes in cyanobacterial CO 2 assimilation: CO 2 concentrating mechanisms and metabolon implications - Clair A. Huffine; Runyu Zhao; Yinjie J. Tang; Jeffrey C. Cameron (Environmental Microbiology, 2023)
Many carbon‐fixing organisms have evolved CO 2 concentrating mechanisms (CCMs) to enhance the delivery of CO 2 to RuBisCO, while minimizing reactions with the competitive inhibitor, molecular O 2 . These distinct types of CCMs have been extensively studied using genetics, biochemistry, cell imaging, mass spectrometry, and metabolic flux analysis. Highlighted in this paper, the cyanobacterial CCM features a bacterial microcompartment (BMC) called ‘carboxysome’ in which RuBisCO is co‐encapsulated with the enzyme carbonic anhydrase (CA) within a semi‐permeable protein shell. The cyanobacterial CCM is capable of increasing CO 2 around RuBisCO, leading to one of the most efficient processes known for fixing ambient CO 2 . The carboxysome life cycle is dynamic and creates a unique subcellular environment that promotes activity of the Calvin–Benson (CB) cycle. The carboxysome may function within a larger cellular metabolon, physical association of functionally coupled proteins, to enhance metabolite channelling and carbon flux. In light of CCMs, synthetic biology approaches have been used to improve enzyme complex for CO 2 fixations. Research on CCM‐associated metabolons has also inspired biologists to engineer multi‐step pathways by providing anchoring points for enzyme cascades to channel intermediate metabolites towards valuable products.

From the basics to emerging diagnostic technologies: What is on the horizon for tilapia disease diagnostics? - Ha Thanh Dong; Thawatchai Chaijarasphong; Andrew C. Barnes; Jérôme Delamare‐Deboutteville; Peiyu Alison Lee; Saengchan Senapin; Chadag Vishnumurthy Mohan; Kathy F. J. Tang; Sharon E. McGladdery; Melba G. Bondad‐Reantaso (Reviews in Aquaculture, 2023)
Tilapia is an affordable protein source farmed in over 140 countries with the majority of production in low‐ and middle‐income countries. Intensification of tilapia farming has exacerbated losses caused by emerging and re‐emerging infectious diseases. Disease diagnostics play a crucial role in biosecurity and health management to mitigate disease loss and improve animal welfare in aquaculture. Three continuous levels of diagnostics (I, II and III) for aquatic species have been proposed by Food and Agriculture Organization of the United Nations (FAO) and the Network of Aquaculture Centers in Asia and the Pacific (NACA) to promote the integration of basic and advanced methods to achieve accurate and meaningful interpretation of diagnostic results. However, the recent proliferation of cutting‐edge molecular methods applied in the diagnosis of diseases of aquacultured animals has shifted the focus of researchers and users away from basic approaches and toward molecular diagnostics, despite the fact that many diseases can be rapidly diagnosed using inexpensive, simple microscopic examination and that most emerging diseases in aquaculture were discovered by histopathology. This review, therefore, revisits and highlights the importance of the three levels of diagnostics for diseases of tilapia, particularly the frequently overlooked basic procedures (e.g., case history records, gross pathology, presumptive diagnostic methods and histopathology). The review also covers current and emerging molecular diagnostic technologies for tilapia pathogens including polymerase chain reaction methods (conventional, quantitative, digital), isothermal amplification methods Loop‐mediated Isothermal Amplification (LAMP), recombinase polymerase amplification (RPA), clustered regularly interspaced short palindromic repeats (CRISPR)‐based detection, lateral flow immunoassays, as well as discussing what is on the horizon for tilapia disease diagnostics (next generation sequencing, artificial intelligence, environmental Deoxyribonucleic Acid (DNA) and Ribonucleic Acid (RNA) and point‐of‐care testing) providing a future vision for transferring these technologies to farmers and stakeholders for a sustainable aquatic food system transformation.

Spatial and seasonal variations in the carbon and lead isotopes of PM2.5 in air of residential buildings and their applications for source identification - Chien-Cheng Jung; Yang-Hsueh Chen; Charles C.-K. Chou; Yi-Tang Huang; Kuan-Ting Lin (Environmental Pollution, 2023)

Analytical and experimental study of a metamaterial beam with grading piezoelectric transducers for vibration attenuation band widening - Yupei Jian; Guobiao Hu; Lihua Tang; Wei Tang; Moein Abdi; Kean C. Aw (Engineering Structures, 2023)

Recent Developments in Additive-Manufactured Intermetallic Compounds for Bio-Implant Applications - Po-Yuan Yeh; Jacob C. Huang; Jason S. C. Jang; Cheng-Tang Pan; Chung-Hwan Chen; Che-Hsin Lin (Journal of Medical and Biological Engineering, 2022)
Purpose This paper reviews the recent developments of two newly developed intermetallic compounds (IMCs) of metallic glasses (MGs) and high-entropy alloys (HEAs) as potential implantable biomaterials. Methods The paper commences by summarizing the fundamental properties of recently developed MGs and high-entropy alloys (HEAs). A systematic review is presented of the recent literature about the use of AM technology in fabricating MG and HEA components for biological implant applications. Results The high strength, low Young’s modulus, and excellent corrosion resistance make these IMCs good candidates as bio-implantable materials. Recent studies have shown that additive manufacturing (AM) techniques provide an advantageous route for the preparation of glassy metallic components due to their intrinsically rapid cooling rates and ability to fabricate parts with virtually no size or complexity constraints. A practical example is conducted by AM producing a porous gradient Ti-based MG spinal cage. The produced MG powders and the in vivo test results on an 18 M-old Lanyu pig confirm the feasibility of the AM technique for producing implantable IMC-based prosthesis. Conclusion The non-crystalline structure of MGs alloy and the random crystalline composition of HEAs provide unique material properties that will substantially impact the development of future implantable prostheses.

Genetic screening of relatives of decedents experiencing sudden unexpected death: medical examiner’s office referrals to a multi-disciplinary cardiogenetics program - Tamar Siskind; Nori Williams; Monisha Sebastin; Robert Marion; Thomas V. McDonald; Christine Walsh; Barbara Sampson; Yingying Tang; Bradley C. Clark (Journal of Community Genetics, 2022)

Soil Carbon within the Mangrove Landscape in Rufiji River Delta, Tanzania - Zhaohua Dai; Carl C. Trettin; Mwita M. Mangora; Wenwu Tang (Wetlands, 2022)
Mangroves are among the most carbon-rich terrestrial ecosystems, primarily attributable to the soil pool. There are substantial differences in soil carbon (C) and nitrogen (N) due to the disparities in geomorphic settings and ecological drivers, but this insight is drawn primarily from observational studies. An objective inventory of carbon stocks in mangroves of the Rufiji River Delta, Tanzania was conducted. Seventy-five soil cores were collected within a 12,164 ha inventory area, comprising the northern portion of the delta. Cores were collected from intact and dwarf mangroves, agricultural fields, and mudflats. The spatial mean soil organic carbon (SOC) density in mangroves was 16.35 ± 6.25 mg C cm −3 . Mean SOC density in non-vegetated mudflats was 12.16 ± 4.57 mg C cm −3 , demonstrating that mangroves develop on soils with a substantial soil C stock. However, long-established mangroves had had a higher C density (17.27 ± 5.87 mg C cm −3 ). Using a δ 13 C mixing model, the source of soil organic matter in mudflats was primarily marine, while long-established mangroves was predominantly mangrove. There were small differences in SOC among long-established mangrove sites in different geomorphic settings. The proportion of marine-sourced SOC increased with soil depth in mangroves. The SOC and nitrogen of agricultural sites resemble those of mudflats, suggesting those sites are developed from relatively young forests. The SOC and nitrogen density in dwarf mangrove sites were lower than others, perhaps reflecting past disturbances.

Effects of transcranial direct current stimulation on brain changes and relation to cognition in patients with schizophrenia: a fMRI study - Yong Liu; Hechun Li; Wei Li; Yiran Wang; Jiangling Jiang; Xinyi Cao; Tianhong Zhang; Yingying Tang; Jijun Wang; Dezhong Yao; Cheng Luo; Robert C. Smith; et al. (Brain Imaging and Behavior, 2022)

Nitrous oxide production in the Chesapeake Bay - Weiyi Tang; John C. Tracey; Julia Carroll; Elizabeth Wallace; Jenna A. Lee; Levy Nathan; Xin Sun; Amal Jayakumar; Bess B. Ward (Limnology and Oceanography, 2022)
Estuaries at the global scale are significant but highly uncertain sources of atmospheric nitrous oxide (N 2 O), which is an intense greenhouse gas and ozone depletion agent. As the largest estuary in the United States, the Chesapeake Bay is suggested to be a spatially and temporally variable source and sink of N 2 O. However, limited observations of N 2 O cycling preclude us from estimating and predicting its net N 2 O flux. To improve our mechanistic understanding of the processes that control the N 2 O flux at the point of production, we applied multiple 15 N tracers (, 15 N‐urea, and ) to separately track N 2 O production from nitrification and denitrification under in situ and manipulated O 2 concentrations in the Chesapeake Bay. Nitrification was the major N 2 O production pathway in oxic waters (up to 7.5 nmol N 2 O L −1 d −1 ). In contrast, denitrification dominated N 2 O production from hypoxic/anoxic waters (up to 20 nmol N 2 O L −1 d −1 ). N 2 O production from urea was observed for the first time in estuarine waters. The contribution from urea was small, but interestingly, showed a depth pattern distinct from other N 2 O precursors. Experimentally lowering the O 2 concentration substantially enhanced N 2 O production. Therefore, the expansion of hypoxic and anoxic zones in the Chesapeake Bay under climate change as suggested by some climate models may favor the production of N 2 O, potentially providing positive feedback on warming. Overall, our study provides mechanistic constraints on N 2 O dynamics that could benefit modeling studies to better estimate the N 2 O flux in the Chesapeake Bay and other coastal environments.

Correction to: Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Rastogi; Sunny Nguyen; et al. (GeroScience, 2022)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Evaluation of design options for green product development: a combined Cuckoo search and life cycle assessment approach - C. Y. Ng; W. C. Tang (The International Journal of Life Cycle Assessment, 2022)

Secondary metabolites: a boon from plants, the best chemist in nature: preface from the editors - S. Ochatt; A. R. Alan; A. Bhattacharya; C. Hano; K. V. Kiselev; P. L. Marconi; W. C. Otoni; S. Y. Park; K. X. Tang; P. J. Weathers (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Association between antidepressant use and second breast cancer event after ductal carcinoma in situ diagnosis: a nested case–control study - Elizabeth T. Mansi; Kathleen E. Malone; Mei-Tzu Tang; Nicole C. Loroña; Christopher I. Li (Cancer Causes & Control, 2022)

Distinct Effects of the Hippocampal Transplantation of Neural and Mesenchymal Stem Cells in a Transgenic Model of Alzheimer’s Disease - Henrique C. Campos; Deidiane Elisa Ribeiro; Debora Hashiguchi; Deborah Y. Hukuda; Christiane Gimenes; Simone A. A. Romariz; Qing Ye; Yong Tang; Henning Ulrich; Beatriz Monteiro Longo (Stem Cell Reviews and Reports, 2022)

Correction to: A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility - Mathew Birdsall Abrams; Jan G. Bjaalie; Samir Das; Gary F. Egan; Satrajit S. Ghosh; Wojtek J. Goscinski; Jeffrey S. Grethe; Jeanette Hellgren Kotaleski; Eric Tatt Wei Ho; David N. Kennedy; Linda J. Lanyon; Trygve B. Leergaard; et al. (Neuroinformatics, 2022)

A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility - Mathew Birdsall Abrams; Jan G. Bjaalie; Samir Das; Gary F. Egan; Satrajit S. Ghosh; Wojtek J. Goscinski; Jeffrey S. Grethe; Jeanette Hellgren Kotaleski; Eric Tatt Wei Ho; David N. Kennedy; Linda J. Lanyon; Trygve B. Leergaard; et al. (Neuroinformatics, 2022)
There is great need for coordination around standards and best practices in neuroscience to support efforts to make neuroscience a data-centric discipline. Major brain initiatives launched around the world are poised to generate huge stores of neuroscience data. At the same time, neuroscience, like many domains in biomedicine, is confronting the issues of transparency, rigor, and reproducibility. Widely used, validated standards and best practices are key to addressing the challenges in both big and small data science, as they are essential for integrating diverse data and for developing a robust, effective, and sustainable infrastructure to support open and reproducible neuroscience. However, developing community standards and gaining their adoption is difficult. The current landscape is characterized both by a lack of robust, validated standards and a plethora of overlapping, underdeveloped, untested and underutilized standards and best practices. The International Neuroinformatics Coordinating Facility (INCF), an independent organization dedicated to promoting data sharing through the coordination of infrastructure and standards, has recently implemented a formal procedure for evaluating and endorsing community standards and best practices in support of the FAIR principles. By formally serving as a standards organization dedicated to open and FAIR neuroscience, INCF helps evaluate, promulgate, and coordinate standards and best practices across neuroscience. Here, we provide an overview of the process and discuss how neuroscience can benefit from having a dedicated standards body.

Spatial Association Between Orogenic Gold Mineralization and Structures Revealed by 3D Prospectivity Modeling: A Case Study of the Xiadian Gold Deposit, Jiaodong Peninsula, China - Zhankun Liu; Jin Chen; Xiancheng Mao; Lei Tang; Shuyan Yu; Hao Deng; Jinli Wang; Yuqiao Liu; Shoulei Li; Richard C. Bayless (Natural Resources Research, 2021)

Antihypertensive medications and risks of recurrence and mortality in luminal, triple-negative, and HER2-overexpressing breast cancer - Nicole C. Lorona; Linda S. Cook; Mei-Tzu C. Tang; Deirdre A. Hill; Charles L. Wiggins; Christopher I. Li (Cancer Causes & Control, 2021)

Current treatment of IgA nephropathy - Jürgen Floege; Thomas Rauen; Sydney C. W. Tang (Seminars in Immunopathology, 2021)
IgA nephropathy (IgAN) is the most common type of glomerulonephritis in Asia and the Western world. In most patients, it follows an asymptomatic to oligosymptomatic course and GFR loss, if any, is slow. The mainstay of therapy therefore is optimized supportive care, i.e., measures that lower blood pressure, reduce proteinuria, minimize lifestyle risk factors, and otherwise help to reduce non-specific insults to the kidneys. The value of immunosuppression has become controversial and if at all, systemic high-dose corticosteroid therapy should be considered for a few months taking into account patient characteristics that would caution against or preclude such therapy. In addition, adverse events related to corticosteroid therapy markedly increase as GFR declines. Beyond corticosteroids, there is little evidence that any additional immunosuppression is helpful, with the exception of mycophenolate mofetil in patients of Asian descent. A considerable number of clinical trials ranging from enteric coated budesonide to blockade of B-cell function to complement inhibitors are currently ongoing and will hopefully allow a more targeted therapy of high-risk patients with progressive IgAN in the future.

Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Ragosti; Sunny Nguyen; et al. (GeroScience, 2021)

Taurine Reduces Liver Damage in Non-Alcoholic Fatty Liver Disease Model in Rats by Down-Regulating IL-9 and Tumor Growth Factor TGF-β - Z. Yao; G. Liang; Z. L. Lv; L. C. Lan; F. L. Zhu; Q. Tang; L. Huang; X. Q. Chen; M. X. Yang; Q. W. Shan (Bulletin of Experimental Biology and Medicine, 2021)

Effect of DAOA genetic variation on white matter alteration in corpus callosum in patients with first-episode schizophrenia - Wenjun Su; Tianyuan Zhu; Lihua Xu; Yanyan Wei; Botao Zeng; Tianhong Zhang; Huiru Cui; Junjie Wang; Yuping Jia; Jinhong Wang; Donald C. Goff; Yingying Tang; et al. (Brain Imaging and Behavior, 2021)

Delineating the organization of projection neuron subsets in primary visual cortex with multiple fluorescent rabies virus tracing - Liang Li; Yajie Tang; Leqiang Sun; Jinsong Yu; Siheng Zhang; Hui Gong; Hannah C. Webber; Xiaoyu Zhang; Zhe Hu; Xiangning Li; Khaista Rahman; Xiangwei Shi; et al. (Brain Structure and Function, 2021)

Electric Field Stimulation for the Functional Assessment of Isolated Dorsal Root Ganglion Neuron Excitability - Ian M. Berke; Tom M. McGrath; J. Jordan Stivers; Chang Gui; Marcos N. Barcellona; Matthew G. Gayoso; Simon Y. Tang; Yu-Qing Cao; Munish C. Gupta; Lori A. Setton (Annals of Biomedical Engineering, 2021)

Assessment of shale gas potential of the lower Permian transitional Shanxi-Taiyuan shales in the southern North China Basin - P. Li; J. C. Zhang; X. Tang; Z. P. Huo; Z. Li; K. Y. Luo; Z. M. Li (Australian Journal of Earth Sciences, 2021)

Slow-released bio-organic–chemical fertilizer improved tomato growth: synthesis and pot evaluations - Xinying Wang; Yuechao Yang; Bin Gao; Yongshan Wan; Yuncong C. Li; Jiazhuo Xie; Yafu Tang (Journal of Soils and Sediments, 2021)

A Bornean peat swamp forest is a net source of carbon dioxide to the atmosphere - Angela C. I. Tang; Lulie Melling; Paul C. Stoy; Kevin K. Musin; Edward B. Aeries; Joseph W. Waili; Mariko Shimizu; Benjamin Poulter; Ryuichi Hirata (Global Change Biology, 2020)
Tropical peat forests are a globally important reservoir of carbon, but little is known about CO 2 exchange on an annual basis. We measured CO 2 exchange between the atmosphere and tropical peat swamp forest in Sarawak, Malaysia using the eddy covariance technique over 4 years from 2011 to 2014. The CO 2 fluxes varied between seasons and years. A small carbon uptake took place during the rainy season at the beginning of 2011, while a substantial net efflux of >600 g C/m 2 occurred over a 2 month period in the middle of the dry season. Conversely, the peat ecosystem was a source of carbon during both the dry and rainy seasons in subsequent years and more carbon was lost during the rainy season relative to the dry season. Our results demonstrate that the forest was a net source of CO 2 to the atmosphere during every year of measurement with annual efflux ranging from 183 to 632 g C m −2 year −1 , noting that annual flux values were sensitive to gap filling methodology. This is in contrast to the typical view of tropical peat forests which must have acted as net C sinks over time scales of centuries to millennia to create the peat deposits. Path analyses revealed that the gross primary productivity (GPP) and ecosystem respiration (RE) were primarily affected by vapour pressure deficit (VPD). Results suggest that future increases in VPD could further reduce the C sink strength and result in additional net CO 2 losses from this tropical peat swamp forest in the absence of plant acclimation to such changes in atmospheric dryness.

Microplastics in the soil environment: Occurrence, risks, interactions and fate – A review - Baile Xu; Fei Liu; Zachary Cryder; Dan Huang; Zhijiang Lu; Yan He; Haizhen Wang; Zhenmei Lu; Philip C. Brookes; Caixian Tang; Jay Gan; Jianming Xu (Critical Reviews in Environmental Science and Technology, 2020)

Genetic determinism of prickles in rose - N. N. Zhou; K. X. Tang; J. Jeauffre; T. Thouroude; D. C. Lopez Arias; F. Foucher; L. Hibrand-Saint Oyant (Theoretical and Applied Genetics, 2020)

Metabolic Syndrome Impairs 3D Mitochondrial Structure, Dynamics, and Function in Swine Mesenchymal Stem Cells - Rahele A. Farahani; Mohamed C. Farah; Xiang-Yang Zhu; Hui Tang; Ishran M. Saadiq; Lilach O. Lerman; Alfonso Eirin (Stem Cell Reviews and Reports, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Determining Haemodynamic Wall Shear Stress in the Rabbit Aorta In Vivo Using Contrast-Enhanced Ultrasound Image Velocimetry - K. Riemer; E. M. Rowland; C. H. Leow; M. X. Tang; P. D. Weinberg (Annals of Biomedical Engineering, 2020)
Abnormal blood flow and wall shear stress (WSS) can cause and be caused by cardiovascular disease. To date, however, no standard method has been established for mapping WSS in vivo . Here we demonstrate wide-field assessment of WSS in the rabbit abdominal aorta using contrast-enhanced ultrasound image velocimetry (UIV). Flow and WSS measurements were made independent of beam angle, curvature or branching. Measurements were validated in an in silico model of the rabbit thoracic aorta with moving walls and pulsatile flow. Mean errors over a cardiac cycle for velocity and WSS were 0.34 and 1.69%, respectively. In vivo time average WSS in a straight segment of the suprarenal aorta correlated highly with simulations (PC = 0.99) with a mean deviation of 0.29 Pa or 5.16%. To assess fundamental plausibility of the measurement, UIV WSS was compared to an analytic approximation derived from the Poiseuille equation; the discrepancy was 17%. Mapping of WSS was also demonstrated in regions of arterial branching. High time average WSS (TAWSS xz = 3.4 Pa) and oscillatory flow (OSI xz = 0.3) were observed near the origin of conduit arteries. In conclusion, we have demonstrated that contrast-enhanced UIV is capable of measuring spatiotemporal variation in flow velocity, arterial wall location and hence WSS in vivo with high accuracy over a large field of view.

Phylogenetic and population genetic analyses reveal three distinct lineages of the invasive brown root-rot pathogen, Phellinus noxius, and bioclimatic modeling predicts differences in associated climate niches - J. E. Stewart; M.-S. Kim; Y. Ota; N. Sahashi; J. W. Hanna; M. Akiba; J. P. Ata; N. Atibalentja; F. Brooks; C.-L. Chung; E. K. Dann; A. Mohd Farid; et al. (European Journal of Plant Pathology, 2020)

Assessing flood risk in Baiyangdian Lake area in a changing climate using an integrated hydrological-hydrodynamic modelling - Y. Wang; X. Zhang; Q. Tang; M. Mu; C. Zhang; A. Lv; S. Jia (Hydrological Sciences Journal, 2019)

Improved rhizoremediation for decabromodiphenyl ether (BDE-209) in E-waste contaminated soils - Jiayin Feng; Xinquan Shen; Jian Chen; Jiachun Shi; Jianming Xu; Caixian Tang; Philip C. Brookes; Yan He (Soil Ecology Letters, 2019)

Biomass and pigments production of a newly isolated photosynthetic bacterium Ectothiorhodospira shaposhnikovii P2 from saline wastewater - J. Cai; Y. Guan; F. Li; Y. Zhao; C. Feng; N. Tang (International Journal of Environmental Science and Technology, 2019)

Association between occupational exposure to trichloroethylene and serum levels of microRNAs: a cross-sectional molecular epidemiology study in China - Kyoung-Mu Lee; Bryan A. Bassig; Luoping Zhang; Roel C. Vermeulen; Wei Hu; Jason Y. Y. Wong; Chuangyi Qiu; Cuiju Wen; Yongshun Huang; Mark P. Purdue; Bu-Tian Ji; Laiyu Li; et al. (International Archives of Occupational and Environmental Health, 2019)

Enhancing nitrogen removal from wastewater in sequencing batch reactors (SBRs) using additional carbon source produced from food waste acidogenic fermentation at different temperatures - Yunhui Pu; Jialing Tang; Xiaochang C. Wang; Yisong Hu; Jin Huang; Shengwang Pan; Yuyou Li (Environmental Science and Pollution Research, 2019)

Combining potassium chloride leaching with vertical electrokinetics to remediate cadmium-contaminated soils - Qiang Ma; Jun Li; Charles C. C. Lee; Xinxian Long; Yongmao Liu; Qi-Tang Wu (Environmental Geochemistry and Health, 2019)

A new water retention model that considers pore non-uniformity and evolution of pore size distribution - Q. Cheng; C. W. W. Ng; C. Zhou; C. S. Tang (Bulletin of Engineering Geology and the Environment, 2019)

A new framework for characterizing landslide deformation: a case study of the Yu-Kai highway landslide in Guizhou, China - Huiming Tang; Wenping Gong; Changdong Li; Liangqing Wang; C. Hsein Juang (Bulletin of Engineering Geology and the Environment, 2019)

Identification and Expression Profiling of Odorant Receptor Protein Genes in Sitophilus zeamais (Coleoptera: Curculionoidea) Using RT-qPCR - Q Tang; Y Zhang; C Shen; D Xia (Neotropical Entomology, 2019)

Evolving and Sustaining Ocean Best Practices and Standards for the Next Decade - Jay Pearlman; Mark Bushnell; Laurent Coppola; Johannes Karstensen; Pier Luigi Buttigieg; Francoise Pearlman; Pauline Simpson; Michele Barbier; Frank E. Muller-Karger; Cristian Munoz-Mas; Peter Pissierssens; Cyndy Chandler; et al. (Frontiers in Marine Science, 2019)

Oil charge history of Paleogene–Eocene reservoir in the Termit Basin (Niger) - J. Liu; G. Zhang; Z. Li; Y. Tang; H. Xiao; H. Lai; C. Yang (Australian Journal of Earth Sciences, 2019)

Minimum Scanline-to-Fracture Angle and Sample Size Required to Produce a Highly Accurate Estimate of the 3-D Fracture Orientation Distribution - Lei Huang; Huiming Tang; Liangqing Wang; C. H. Juang (Rock Mechanics and Rock Engineering, 2019)

Real time monitoring of Aeromonas salmonicida evolution in response to successive antibiotic therapies in a commercial fish farm - Xiaochen Du; Sion C. Bayliss; Edward J. Feil; Ying Liu; Chao Wang; Gang Zhang; Dongsheng Zhou; Dawei Wei; Na Tang; Sébastien O. Leclercq; Jie Feng (Environmental Microbiology, 2019)
Summary Our ability to predict evolutionary trajectories of pathogens in response to antibiotic pressure is one of the promising leverage to fight against the present antibiotic resistance worldwide crisis. Yet, few studies tackled this question in situ at the outbreak level, due to the difficulty to link a given pathogenic clone evolution with its precise antibiotic exposure over time. In this study, we monitored the real‐time evolution of an Aeromonas salmonicida clone in response to successive antibiotic and vaccine therapies in a commercial fish farm. The clone was responsible for a four‐year outbreak of furunculosis within a Recirculating Aquaculture System Salmo salar farm in China, and we reconstructed the precise tempo of mobile genetic elements (MGEs) acquisition events during this period. The resistance profile provided by the acquired MGEs closely mirrored the antibiotics used to treat the outbreak, and we evidenced that two subclonal groups developed similar resistances although unrelated MGE acquisitions. Finally, we also demonstrated the efficiency of vaccination in outbreak management and its positive effect on antibiotic resistance prevalence. Our study provides unprecedented knowledge critical to understand evolutionary trajectories of resistant pathogens outside the laboratory.

On-board radiometric calibration for thermal emission band of FY-3C/MERSI - Q. S. Liu; Y. H. Tang; L. Qin; H. S. Dai; Q. C. Zhao; Y. Yang (International Journal of Remote Sensing, 2019)

Reproductive and menopausal factors and risk of second primary breast cancer after in situ breast carcinoma - Michelle L. Baglia; Mei-Tzu C. Tang; Kathleen E. Malone; Peggy Porter; Christopher I. Li (Cancer Causes & Control, 2019)

Potential impacts of climate change on storage conditions for commercial agriculture: an example for potato production in Michigan - Julie A. Winkler; Logan Soldo; Ying Tang; Todd Forbush; David S. Douches; Chris M. Long; Courtney P. Leisner; C. Robin Buell (Climatic Change, 2018)

A hybrid proline-rich cell-wall protein gene JsPRP1 from Juglans sigillata Dode confers both biotic and abiotic stresses in transgenic tobacco plants - D. Q. Liu; Q. Han; T. Shah; C. Y. Chen; Q. Wang; B. F. Tang; F. Ge (Trees, 2018)

The Influence of Water Saturation on the Short- and Long-Term Mechanical Behavior of Red Sandstone - S. B. Tang; C. Y. Yu; M. J. Heap; P. Z. Chen; Y. G. Ren (Rock Mechanics and Rock Engineering, 2018)

Expression of IL-17F is associated with non-pathogenic Th17 cells - Florian Wanke; Yilang Tang; Konrad Gronke; Sabrina Klebow; Sonja Moos; Judith Hauptmann; Arthi Shanmugavadivu; Tommy Regen; Ilgiz A. Mufazalov; Lauren A. Gabriel; Sonja Reißig; Andreas Diefenbach; et al. (Journal of Molecular Medicine, 2018)

Variability in circulating gas emboli after a same scuba diving exposure - V. Papadopoulou; P. Germonpré; D. Cosgrove; R. J. Eckersley; P. A. Dayton; G. Obeid; A. Boutros; M.-X. Tang; S. Theunissen; C. Balestra (European Journal of Applied Physiology, 2018)

Determination of the potential implementation impact of 2016 ministry of environmental protection generic assessment criteria for potentially contaminated sites in China - Yuanyuan Cheng; Yu-Ting Tang; C. Paul Nathanail (Environmental Geochemistry and Health, 2018)

The Pros and Cons of Encouraging Shallow Groundwater Use through Controlled Drainage in a Salt-Impacted Irrigation Area - S. Li; Wan Luo; Z. Jia; S. Tang; C. Chen (Water Resources Management, 2018)

Impact of choice of future climate change projection on growth chamber experimental outcomes: a preliminary study in potato - Courtney P. Leisner; Joshua C. Wood; Brieanne Vaillancourt; Ying Tang; Dave S. Douches; C. Robin Buell; Julie A. Winkler (International Journal of Biometeorology, 2018)

Fishing for contaminants: identification of three mechanism specific transcriptome signatures using Danio rerio embryos - Jonas Hausen; Jens C. Otte; Jessica Legradi; Lixin Yang; Uwe Strähle; Martina Fenske; Markus Hecker; Song Tang; Monika Hammers-Wirtz; Henner Hollert; Steffen H. Keiter; Richard Ottermanns (Environmental Science and Pollution Research, 2018)

Actionable secondary findings from whole-genome sequencing of 954 East Asians - Clara Sze-man Tang; Saloni Dattani; Man-ting So; Stacey S. Cherny; Paul K. H. Tam; Pak C. Sham; Maria-Mercè Garcia-Barcelo (Human Genetics, 2018)

Historical biogeography of Goniothalamus and Annonaceae tribe Annoneae: dispersal–vicariance patterns in tropical Asia and intercontinental tropical disjunctions revisited - Daniel C. Thomas; Chin Cheung Tang; Richard M. K. Saunders (Journal of Biogeography, 2017)
Aim The historical biogeography of the species‐rich flowering plant genus Goniothalamus ( c . 130 species) and the wider Annonaceae tribe Annoneae is investigated to evaluate hypotheses regarding the processes underlying tropical intercontinental disjunctions (‘long‐distance dispersal [ LDD ]’ versus ‘boreotropics’) and floristic exchange between biodiversity hotspots in tropical Asia. Location Tropics, tropical Asia. Methods Divergence time estimation was based on plastid DNA sequence data ( c . 10 kb; 164 Annonaceae accessions, including 65 Goniothalamus species) using an uncorrelated lognormal relaxed clock model and two fossil calibrations. Likelihood ancestral range estimation was performed using dispersal‐extinction‐cladogenesis models with and without time‐stratified dispersal constraints. Results The boreotropics model incorporating high chances for intercontinental dispersal during 68–34 Ma fitted the data significantly better than LDD models enforcing low intercontinental dispersal rates. Multiple vicariance events were identified in Annoneae including at the Annoneae crown node (57–49 Ma, Africa/S+N America), and the Disepalum ‐ Asimina split (27–24 Ma, Asia/N America). A wide ancestral range in continental SE Asia, W and E Malesia was inferred at the Goniothalamus crown node (24–21 Ma). Several dispersal events from continental SE Asia/W Malesia were identified in the Miocene: two north‐eastwards to the Philippines, one eastwards to the Sahul Shelf and two westwards to India. Main conclusions The boreotropics hypothesis provides a well‐supported, plausible explanation for the disjunctions and dispersal–vicariance patterns in tribe Annoneae. The wide distribution inferred at the Goniothalamus crown node indicates that its ancestors already bridged the marine gap between the Sunda and Sahul Shelves by LDD or rafting on tectonic plate microfragments. Dispersal across long‐standing water bodies in Malesia occurred multiple times from the early Miocene as marine gaps decreased following tectonic plate convergence and land emergence. Substantially older crown group divergence estimates compared with previous studies indicate that hypotheses of rapid recent radiation in Goniothalamus must be rejected.

Investigation on Optimally Performing Sensor Substrates through Bio-fouling of Immunoglobulin-Conjugated Gold Nanoparticles - Subash C. B. Gopinath; Ramanujam Kumaresan; Toshiyasu Nishimura; Thangavel Lakshmipriya; Thean-Hock Tang; Yeng Chen; Uda Hashim (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Detection of gastrointestinal pathogens in oncology patients by highly multiplexed molecular panels - C. C. Otto; L. H. Chen; T. He; Y.-W. Tang; N. E. Babady (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

The burden and epidemiology of community-acquired central nervous system infections: a multinational study - H. Erdem; A. Inan; E. Guven; S. Hargreaves; L. Larsen; G. Shehata; E. Pernicova; E. Khan; L. Bastakova; S. Namani; A. Harxhi; T. Roganovic; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Erratum to: Optimizing the Terzaghi Estimator of the 3D Distribution of Rock Fracture Orientations - Huiming Tang; Lei Huang; C. Hsein Juang; Junrong Zhang (Rock Mechanics and Rock Engineering, 2017)

Optimizing the Terzaghi Estimator of the 3D Distribution of Rock Fracture Orientations - Huiming Tang; Lei Huang; C. Hsein Juang; Junrong Zhang (Rock Mechanics and Rock Engineering, 2017)

Erratum to: Intercomparison of the Arctic sea ice cover in global ocean–sea ice reanalyses from the ORA-IP project - Matthieu Chevallier; Gregory C. Smith; Frédéric Dupont; Jean-François Lemieux; Gael Forget; Yosuke Fujii; Fabrice Hernandez; Rym Msadek; K. Andrew Peterson; Andrea Storto; Takahiro Toyoda; Maria Valdivieso; et al. (Climate Dynamics, 2017)

Intercomparison of the Arctic sea ice cover in global ocean–sea ice reanalyses from the ORA-IP project - Matthieu Chevallier; Gregory C. Smith; Frédéric Dupont; Jean-François Lemieux; Gael Forget; Yosuke Fujii; Fabrice Hernandez; Rym Msadek; K. Andrew Peterson; Andrea Storto; Takahiro Toyoda; Maria Valdivieso; et al. (Climate Dynamics, 2017)

Correlated GNSS and temperature measurements at 10-minute intervals on the Severn Suspension Bridge - G. W. Roberts; C. J. Brown; X. Tang (Applied Geomatics, 2017)

A New Method to Evaluate Rock Mass Brittleness Based on Stress–Strain Curves of Class I - Y. J. Xia; L. C. Li; C. A. Tang; X. Y. Li; S. Ma; M. Li (Rock Mechanics and Rock Engineering, 2017)

The short-term effects of liming on organic carbon mineralisation in two acidic soils as affected by different rates and application depths of lime - S. P. Grover; C. R. Butterly; X. Wang; C. Tang (Biology and Fertility of Soils, 2017)

Identification and expression analysis of terminal deoxynucleotidyl transferase in humphead snapper Lutjanus sanguineus - Y. Huang; J. Cai; J. F. Tang; H. Y. Zhang; Z. W. Wang; J. C. Jian; Z. H. Wu; Y. S. Lu (Journal of Fish Biology, 2017)
A tdt gene was identified successfully from humphead snapper Lutjanus sanguineus , which contained 1710 bp encoding a protein of 463 amino acids. Results of quantitative real‐time polymerase chain reaction ( qRT‐PCR ) indicated that tdt mainly expressed in thymus and head kidney and the transcripts of tdt in these tissues were up‐regulated significantly at 36 and 48 h after Vibrio harveyi infection. Meanwhile Tdt‐producing cells were found in thymus and head kidney.

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)

Cross‐scale intercomparison of climate change impacts simulated by regional and global hydrological models in eleven large river basins - F. F. Hattermann; V. Krysanova; S. N. Gosling; R. Dankers; P. Daggupati; C. Donnelly; M. Flörke; S. Huang; Y. Motovilov; S. Buda; T. Yang; C. Müller; et al. (Climatic Change, 2017)

Education is associated with sub-regions of the hippocampus and the amygdala vulnerable to neuropathologies of Alzheimer’s disease - Xiaoying Tang; Vijay R. Varma; Michael I. Miller; Michelle C. Carlson (Brain Structure and Function, 2017)

New insights into the photochemistry of carotenoid spheroidenone in light-harvesting complex 2 from the purple bacterium Rhodobacter sphaeroides - Dariusz M. Niedzwiedzki; Preston L. Dilbeck; Qun Tang; Elizabeth C. Martin; David F. Bocian; C. Neil Hunter; Dewey Holten (Photosynthesis Research, 2017)

Ecosystem fluxes of hydrogen in a mid‐latitude forest driven by soil microorganisms and plants - Laura K. Meredith; Róisín Commane; Trevor F. Keenan; Stephen T. Klosterman; J. William Munger; Pamela H. Templer; Jianwu Tang; Steven C. Wofsy; Ronald G. Prinn (Global Change Biology, 2017)
Molecular hydrogen (H 2 ) is an atmospheric trace gas with a large microbe‐mediated soil sink, yet cycling of this compound throughout ecosystems is poorly understood. Measurements of the sources and sinks of H 2 in various ecosystems are sparse, resulting in large uncertainties in the global H 2 budget. Constraining the H 2 cycle is critical to understanding its role in atmospheric chemistry and climate. We measured H 2 fluxes at high frequency in a temperate mixed deciduous forest for 15 months using a tower‐based flux‐gradient approach to determine both the soil‐atmosphere and the net ecosystem flux of H 2 . We found that Harvard Forest is a net H 2 sink (−1.4 ± 1.1 kg H 2 ha −1 ) with soils as the dominant H 2 sink (−2.0 ± 1.0 kg H 2 ha −1 ) and aboveground canopy emissions as the dominant H 2 source (+0.6 ± 0.8 kg H 2 ha −1 ). Aboveground emissions of H 2 were an unexpected and substantial component of the ecosystem H 2 flux, reducing net ecosystem uptake by 30% of that calculated from soil uptake alone. Soil uptake was highly seasonal (July maximum, February minimum), positively correlated with soil temperature and negatively correlated with environmental variables relevant to diffusion into soils (i.e., soil moisture, snow depth, snow density). Soil microbial H 2 uptake was correlated with rhizosphere respiration rates ( r = 0.8, P 2 metabolism yielded up to 2% of the energy gleaned by microbes from carbon substrate respiration. Here, we elucidate key processes controlling the biosphere–atmosphere exchange of H 2 and raise new questions regarding the role of aboveground biomass as a source of atmospheric H 2 and mechanisms linking soil H 2 and carbon cycling. Results from this study should be incorporated into modeling efforts to predict the response of the H 2 soil sink to changes in anthropogenic H 2 emissions and shifting soil conditions with climate and land‐use change.

Heat, water and carbon exchanges in the tall megacity of Shanghai: challenges and results - Xiangyu Ao; C. S. B. Grimmond; Yuanyong Chang; Dongwei Liu; Yuqi Tang; Ping Hu; Yadong Wang; Jun Zou; Jianguo Tan (International Journal of Climatology, 2016)
The observed surface energy balance fluxes are essential to improve model forecasting ability but such data are scarce for subtropical cities and urban areas with tall buildings. One year of eddy covariance flux data for an area within Shanghai with a wide range of building heights (8–150 m, mean by direction) are analysed by wind direction. Consideration is given to how to distinguish between local‐ and micro‐scale fluxes. At the local‐scale, median daily peaks of sensible heat flux occur in the early afternoon (winter: 87 W m −2 , spring: 205 W m −2 , summer: 292 W m −2 , autumn: 135 W m −2 ). The latent heat flux is small in winter (median daily maxima 21 W m −2 ) and slightly larger in spring, summer and autumn (49, 65, 49 W m −2 , respectively). The monthly mean daytime Bowen ratio under all‐sky conditions ranges from 2 to 4.7. At this site, with predominately impervious surface (85% buildings/pavement, 14% vegetation), the enhancement of evaporation following rainfall usually lasts for about 12 h. Consistently larger Bowen ratios at the micro‐scale than the local‐scale are attributed to roughness effects and the impact of extensive areas of dry walls. The daily median CO 2 flux is dominated by traffic emissions, with two peaks associated with morning and evening rush hours. The data provide insights into urban surface controls on momentum, energy and carbon dynamics, with implications for urban planning strategies in the context of rapid global urbanization and climate change.

A multi-center, controlled, randomized, open-label clinical study of levofloxacin for preventing infection during the perioperative period of ultrasound-guided transrectal prostate biopsy - L.-D. Qiao; S. Chen; X.-F. Wang; W.-M. Yang; Y.-J. Niu; C.-Z. Kong; W. Tang; X.-F. Gao; B.-K. Shi; Y.-Q. Na; X.-D. Zhang; J.-Y. Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Numerical SHPB Tests of Rocks Under Combined Static and Dynamic Loading Conditions with Application to Dynamic Behavior of Rocks Under In Situ Stresses - J. B. Zhu; Z. Y. Liao; C. A. Tang (Rock Mechanics and Rock Engineering, 2016)

Determination of Dynamic Compressive and Tensile Behavior of Rocks from Numerical Tests of Split Hopkinson Pressure and Tension Bars - Z. Y. Liao; J. B. Zhu; K. W. Xia; C. A. Tang (Rock Mechanics and Rock Engineering, 2016)

Pore-scale and continuum simulations of solute transport micromodel benchmark experiments - M. Oostrom; Y. Mehmani; P. Romero-Gomez; Y. Tang; H. Liu; H. Yoon; Q. Kang; V. Joekar-Niasar; M. T. Balhoff; T. Dewers; G. D. Tartakovsky; E. A. Leist; et al. (Computational Geosciences, 2016)

Effects of additional fermented food wastes on nitrogen removal enhancement and sludge characteristics in a sequential batch reactor for wastewater treatment - Yongmei Zhang; Xiaochang C. Wang; Zhe Cheng; Yuyou Li; Jialing Tang (Environmental Science and Pollution Research, 2016)

Molecular cloning and characterization of lymphocyte cell kinase from humphead snapper ( Lutjanus sanguineus ) - Y Huang; J Cai; B Wang; J‐F Tang; J‐C Jian; Z‐H Wu; Z Gan; Y‐S Lu (Journal of Fish Diseases, 2016)
Lymphocyte cell kinase ( LCK ) belongs to the Src family of tyrosine kinases, which involves in the proliferation control of lymphocytes. In this study, we cloned the LCK gene of humphead snapper ( Lutjanus sanguineus ) (designed as Ls LCK ). Sequence analysis showed that the full‐length cDNA of Ls LCK was 2279 bp, contained a 1506‐bp open reading frame ( ORF ), encoding a polypeptide of 501 amino acids. The deduced amino acid possessed the typical structural features of known LCK proteins, including four Src homology ( SH ) domains arranged as the SH 1 domain followed by a regulatory C‐terminal tail ( COOH ‐domain), SH 2 and SH 3 adapter domains and SH 4 domain which required for membrane attachment and CD 4/ CD 8 binding. Fluorescent quantitative real‐time PCR analysis indicated that Ls LCK transcripts were expressed mainly in thymus, spleen and head kidney in healthy fish. Moreover, the mRNA expressions in these tissues were significantly up‐regulated after challenge with Vibrio harveyi . The results of immunohistochemistry showed that Ls LCK protein localized distinctly in cytoplasm of cell in thymus, spleen and head kidney. Taken together, these findings indicated that Ls LCK may play an important role in the immune response of humphead snapper against bacterial infection.

Zika virus and neural developmental defects: building a case for a cause - Sarah C. Ogden; Christy Hammack; Hengli Tang (Science China Life Sciences, 2016)

The assessment of mangrove biomass and carbon in West Africa: a spatially explicit analytical framework - Wenwu Tang; Wenpeng Feng; Meijuan Jia; Jiyang Shi; Huifang Zuo; Carl C. Trettin (Wetlands Ecology and Management, 2016)

Improved detection of deeply invasive candidiasis with DNA aptamers specific binding to (1→3)-β-D-glucans from Candida albicans - X.-L. Tang; Y. Hua; Q. Guan; C.-H. Yuan (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Repositioning “old” drugs for new causes: identifying new inhibitors of prostate cancer cell migration and invasion - Esha T. Shah; Akanksha Upadhyaya; Lisa K. Philp; Tiffany Tang; Dubravka Skalamera; Jennifer Gunter; Colleen C. Nelson; Elizabeth D. Williams; Brett G. Hollier (Clinical & Experimental Metastasis, 2016)

Long-term effect of lime application on the chemical composition of soil organic carbon in acid soils varying in texture and liming history - X. Wang; C. Tang; J. A. Baldock; C. R. Butterly; C. Gazey (Biology and Fertility of Soils, 2016)

Microseismic Monitoring of Strainburst Activities in Deep Tunnels at the Jinping II Hydropower Station, China - N. W. Xu; T. B. Li; F. Dai; R. Zhang; C. A. Tang; L. X. Tang (Rock Mechanics and Rock Engineering, 2016)

Establishment and characterization of feeder cell-dependent bovine fetal liver cell lines - Neil C. Talbot; Ling Wang; Wesley M. Garrett; Thomas J. Caperna; Young Tang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Visual detection technique for efficient screening and isolation of Salmonella based on a novel enrichment assay using chromatography membrane - F. Tang; Y. Xiong; H. Zhang; K. Wu; Y. Xiang; J.-B. Shao; H.-W. Ai; Y.-P. Xiang; X.-L. Zheng; J.-R. Lv; H. Sun; L.-S. Bao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Analysis of the genome sequence of infectious hematopoietic necrosis virus HLJ-09 in China - C. Wang; L. L. Zhao; Y. J. Li; L. J. Tang; X. Y. Qiao; Y. P. Jiang; M. Liu (Virus Genes, 2016)

EDARV370A associated facial characteristics in Uyghur population revealing further pleiotropic effects - Qianqian Peng; Jinxi Li; Jingze Tan; Yajun Yang; Manfei Zhang; Sijie Wu; Yu Liu; Juan Zhang; Pengfei Qin; Yaqun Guan; Yi Jiao; Zhaoxia Zhang; et al. (Human Genetics, 2016)

A Mesostructure-based Damage Model for Thermal Cracking Analysis and Application in Granite at Elevated Temperatures - Q. L. Yu; P. G. Ranjith; H. Y. Liu; T. H. Yang; S. B. Tang; C. A. Tang; S. Q. Yang (Rock Mechanics and Rock Engineering, 2015)

Cloning, expression, and characterization of Pseudomonas vesicularis MA103 β-1,3-xylanase in Escherichia coli ClearColi BL21(DE3) - Wen-Sing Liang; Tsuei-Yun Fang; Hong-Ting Lin; Tristan C. Liu; Wen-Jung Lu; Wen-Shyong Tzou; Shye-Jye Tang; Fu-Pang Lin; Shiu-Mei Liu; Chorng-Liang Pan (Fisheries Science, 2015)

Impact of Predator Cues on Responses to Silver Nanoparticles in Daphnia carinata - Guangqiu Qin; Yunxia Xiong; Song Tang; Peng Zhao; Jon A. Doering; Shawn C. Beitel; Markus Hecker; Mao Wang; Hongling Liu; Haoliang Lu; Huamao Du (Archives of Environmental Contamination and Toxicology, 2015)

A Real-Time Analysis and Feedback System for Quality Control of Dam Foundation Grouting Engineering - D. H. Zhong; F. G. Yan; M. C. Li; C. X. Huang; K. Fan; J. F. Tang (Rock Mechanics and Rock Engineering, 2015)

A review of the plant virus, viroid, liberibacter and phytoplasma records for New Zealand - S. Veerakone; J. Z. Tang; L. I. Ward; L. W. Liefting; Z. Perez-Egusquiza; B. S. M. Lebas; C. Delmiglio; J. D. Fletcher; P. L. Guy (Australasian Plant Pathology, 2015)

Combined blockade of angiotensin II and prorenin receptors ameliorates podocytic apoptosis induced by IgA-activated mesangial cells - Joseph C. K. Leung; Loretta Y. Y. Chan; M. A. Saleem; P. W. Mathieson; Sydney C. W. Tang; Kar Neng Lai (Apoptosis, 2015)

The effect of Bt-transgene introgression on plant growth and reproduction in wild Brassica juncea - Yong-Bo Liu; Henry Darmency; C. Neal Stewart; Wei Wei; Zhi-Xi Tang; Ke-Ping Ma (Transgenic Research, 2015)

Chronic administration of ketamine mimics the perturbed sense of body ownership associated with schizophrenia - Jinsong Tang; Hannah L. Morgan; Yanhui Liao; Philip R. Corlett; Dong Wang; Hong Li; Yanqing Tang; Jindong Chen; Tieqiao Liu; Wei Hao; Paul C. Fletcher; Xiaogang Chen (Psychopharmacology, 2015)

Astrocytic Cx 43 and Cx 40 in the mouse hippocampus during and after pilocarpine-induced status epilepticus - X. L. Wu; Y. C. Tang; Q. Y. Lu; X. L. Xiao; T. B. Song; F. R. Tang (Experimental Brain Research, 2015)

Linking shelf delta to deep-marine deposition in reservoir dispersal of the upper Oligocene strata in the Baiyun Sag, the northern South China Sea - S. H. Xu; Y. M. Wang; G. Q. Xu; G. D. Zeng; W. Guo; C. L. Gong; C. E. Cai; W. Tang; H. T. Zhuo; H. Q. Wan (Australian Journal of Earth Sciences, 2015)

Effect of grazing on the abundance of functional genes associated with N cycling in three types of grassland in Inner Mongolia - K. Ding; L. Zhong; X. P. Xin; Z. H. Xu; X. M. Kang; W. J. Liu; Y. C. Rui; L. L. Jiang; L. Tang; Y. F. Wang (Journal of Soils and Sediments, 2015)

A Perspective on the Clinical Translation of Scaffolds for Tissue Engineering - Matthew J. Webber; Omar F. Khan; Stefanie A. Sydlik; Benjamin C. Tang; Robert Langer (Annals of Biomedical Engineering, 2015)

Uncertainties in predicting rice yield by current crop models under a wide range of climatic conditions - Tao Li; Toshihiro Hasegawa; Xinyou Yin; Yan Zhu; Kenneth Boote; Myriam Adam; Simone Bregaglio; Samuel Buis; Roberto Confalonieri; Tamon Fumoto; Donald Gaydon; Manuel Marcaida; et al. (Global Change Biology, 2015)
Predicting rice ( Oryza sativa ) productivity under future climates is important for global food security. Ecophysiological crop models in combination with climate model outputs are commonly used in yield prediction, but uncertainties associated with crop models remain largely unquantified. We evaluated 13 rice models against multi‐year experimental yield data at four sites with diverse climatic conditions in Asia and examined whether different modeling approaches on major physiological processes attribute to the uncertainties of prediction to field measured yields and to the uncertainties of sensitivity to changes in temperature and CO 2 concentration [ CO 2 ]. We also examined whether a use of an ensemble of crop models can reduce the uncertainties. Individual models did not consistently reproduce both experimental and regional yields well, and uncertainty was larger at the warmest and coolest sites. The variation in yield projections was larger among crop models than variation resulting from 16 global climate model‐based scenarios. However, the mean of predictions of all crop models reproduced experimental data, with an uncertainty of less than 10% of measured yields. Using an ensemble of eight models calibrated only for phenology or five models calibrated in detail resulted in the uncertainty equivalent to that of the measured yield in well‐controlled agronomic field experiments. Sensitivity analysis indicates the necessity to improve the accuracy in predicting both biomass and harvest index in response to increasing [ CO 2 ] and temperature.

Functional network analysis of obese and lean Göttingen minipigs elucidates changes in oxidative and inflammatory networks in obese pigs - Harrie C. M. Boonen; Sophia G. Moesgaard; Malene M. Birck; Berit Ø. Christoffersen; Susanna Cirera; Peter M. H. Heegaard; Tina Rødgaard Højbøge; Lars J. Jensen; Alan Mortensen; Lisbeth Høier Olsen; Majid Sheykhzade; Jiaowei Tang; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

Asymmetric sensitivity of first flowering date to warming and cooling in alpine plants - S. P. Wang; F. D. Meng; J. C. Duan; Y. F. Wang; X. Y. Cui; S. L. Piao; H. S. Niu; G. P. Xu; C. Y. Luo; Z. H. Zhang; X. X. Zhu; M. G. Shen; et al. (Ecology, 2014)
Understanding how flowering phenology responds to warming and cooling (i.e., symmetric or asymmetric response) is needed to predict the response of flowering phenology to future climate change that will happen with the occurrence of warm and cold years superimposed upon a long‐term trend. A three‐year reciprocal translocation experiment was performed along an elevation gradient from 3200 m to 3800 m in the Tibetan Plateau for six alpine plants. Transplanting to lower elevation (warming) advanced the first flowering date (FFD) and transplanting to higher elevation (cooling) had the opposite effect. The FFD of early spring flowering plants (ESF) was four times less sensitive to warming than to cooling (by −2.1 d/°C and 8.4 d/°C, respectively), while midsummer flowering plants (MSF) were about twice as sensitive to warming than to cooling (−8.0 d/°C and 4.9 d/°C, respectively). Compared with pooled warming and cooling data, warming alone significantly underpredicted 3.1 d/°C for ESF and overestimated 1.7 d/°C for MSF. These results suggest that future empirical and experimental studies should consider nonlinear temperature responses that can cause such warming–cooling asymmetries as well as differing life strategies (ESF vs. MSF) among plant species.

Three-Dimensional Numerical Investigations of the Failure Mechanism of a Rock Disc with a Central or Eccentric Hole - S. Y. Wang; S. W. Sloan; C. A. Tang (Rock Mechanics and Rock Engineering, 2014)

Block caving-induced strata movement and associated surface subsidence: a numerical study based on a demonstration model - L. C. Li; C. A. Tang; X. D. Zhao; M. Cai (Bulletin of Engineering Geology and the Environment, 2014)

Albumin and glycated albumin activate KIM-1 release in tubular epithelial cells through distinct kinetics and mechanisms - Ai Ing Lim; Loretta Y. Y. Chan; Sydney C. W. Tang; Kar Neng Lai; Joseph C. K. Leung (Inflammation Research, 2014)

Application of SRAP markers in the identification of Stylosanthes guianensis hybrids - C. Q. Huang; G. D. Liu; C. J. Bai; W. Q. Wang; J. Tang (Molecular Biology Reports, 2014)

Quantitative trait locus analysis of nitrogen use efficiency in barley (Hordeum vulgare L.) - Gashu Aynalem Kindu; Jianjun Tang; Xinyou Yin; Paul C. Struik (Euphytica, 2014)

A White Paper—Consensus and Recommendations of a Global Harmonization Team on Assessing the Impact of Immunogenicity on Pharmacokinetic Measurements - J. M. Sailstad; L. Amaravadi; A. Clements-Egan; B. Gorovits; H. A. Myler; R. C. Pillutla; S. Pursuhothama; M. Putman; M. K. Rose; K. Sonehara; L. Tang; J. T. Wustner (The AAPS Journal, 2014)

Erratum to: RET and NRG1 interplay in Hirschsprung disease - Hongsheng Gui; Wai-Kiu Tang; Man-Ting So; Petroola Proitsi; Pak C. Sham; Paul K. Tam; Elly Sau-Wai Ngan; Stacey S. Cherny; Maria-Mercè Garcia-Barceló (Human Genetics, 2014)

Intraperitoneal delivery of paclitaxel by poly(ether-anhydride) microspheres effectively suppresses tumor growth in a murine metastatic ovarian cancer model - Ming Yang; Tao Yu; Joseph Wood; Ying-Ying Wang; Benjamin C. Tang; Qi Zeng; Brian W. Simons; Jie Fu; Chi-Mu Chuang; Samuel K. Lai; T.-C. Wu; Chien-Fu Hung; et al. (Drug Delivery and Translational Research, 2014)

The Dynamic Evaluation of Rock Slope Stability Considering the Effects of Microseismic Damage - N. W. Xu; F. Dai; Z. Z. Liang; Z. Zhou; C. Sha; C. A. Tang (Rock Mechanics and Rock Engineering, 2014)

Correlations between algae and water quality: factors driving eutrophication in Lake Taihu, China - Y. P. Li; C. Y. Tang; Z. B. Yu; K. Acharya (International Journal of Environmental Science and Technology, 2014)

An integrated model to assess critical rainfall thresholds for run-out distances of debris flows - Th. W. J. van Asch; C. Tang; D. Alkema; J. Zhu; W. Zhou (Natural Hazards, 2014)

The structure of Pavlovian fear conditioning in the amygdala - Hadley C. Bergstrom; Craig G. McDonald; Smita Dey; Haying Tang; Reed G. Selwyn; Luke R. Johnson (Brain Structure and Function, 2013)

Land subsidence caused by internal soil erosion owing to pumping confined aquifer groundwater during the deep foundation construction in Shanghai - X.-S. Zhang; J.-X. Wang; H. Wong; C.-J. Leo; Q. Liu; Y.-Q. Tang; X.-L. Yan; W.-H. Sun; Z.-Q. Huang; X.-H. Hao (Natural Hazards, 2013)

Experimental study on cascading landslide dam failures by upstream flows - Gordon G. D. Zhou; P. Cui; H. Y. Chen; X. H. Zhu; J. B. Tang; Q. C. Sun (Landslides, 2013)

The adaptive variant EDARV370A is associated with straight hair in East Asians - Jingze Tan; Yajun Yang; Kun Tang; Pardis C. Sabeti; Li Jin; Sijia Wang (Human Genetics, 2013)

Reliable, verifiable and efficient monitoring of biodiversity via metabarcoding - Yinqiu Ji; Louise Ashton; Scott M. Pedley; David P. Edwards; Yong Tang; Akihiro Nakamura; Roger Kitching; Paul M. Dolman; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; Wayne W. Hsu; et al. (Ecology Letters, 2013)
To manage and conserve biodiversity, one must know what is being lost, where, and why, as well as which remedies are likely to be most effective. Metabarcoding technology can characterise the species compositions of mass samples of eukaryotes or of environmental DNA . Here, we validate metabarcoding by testing it against three high‐quality standard data sets that were collected in Malaysia (tropical), China (subtropical) and the United Kingdom (temperate) and that comprised 55,813 arthropod and bird specimens identified to species level with the expenditure of 2,505 person‐hours of taxonomic expertise. The metabarcode and standard data sets exhibit statistically correlated alpha‐ and beta‐diversities, and the two data sets produce similar policy conclusions for two conservation applications: restoration ecology and systematic conservation planning. Compared with standard biodiversity data sets, metabarcoded samples are taxonomically more comprehensive, many times quicker to produce, less reliant on taxonomic expertise and auditable by third parties, which is essential for dispute resolution.

Numerical Modeling of Pore Pressure Influence on Fracture Evolution in Brittle Heterogeneous Rocks - S. Y. Wang; S. W. Sloan; S. G. Fityus; D. V. Griffiths; C. A. Tang (Rock Mechanics and Rock Engineering, 2013)

Pneumonia caused by Aeromonas species in Taiwan, 2004–2011 - C. M. Chao; C. C. Lai; H. Y. Tsai; C. J. Wu; H. J. Tang; W. C. Ko; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

QTL analysis of the spring wheat “Chapio” identifies stable stripe rust resistance despite inter-continental genotype × environment interactions - E.-N. Yang; G. M. Rosewarne; S. A. Herrera-Foessel; J. Huerta-Espino; Z.-X. Tang; C.-F. Sun; Z.-L. Ren; R. P. Singh (Theoretical and Applied Genetics, 2013)

Monazite and xenotime U–Th–Pb geochronology by ion microprobe: dating highly fractionated granites at Xihuashan tungsten mine, SE China - Q. L. Li; X. H. Li; Z. W. Lan; C. L. Guo; Y. N. Yang; Y. Liu; G. Q. Tang (Contributions to Mineralogy and Petrology, 2013)

3D modeling of stratified and irregularly jointed rock slope and its progressive failure - K. Ma; C. A. Tang; L. C. Li; P. G. Ranjith; M. Cai; N. W. Xu (Arabian Journal of Geosciences, 2013)

The contribution of crop residues to changes in soil pH under field conditions - C. R. Butterly; J. A. Baldock; C. Tang (Plant and Soil, 2013)

Levels, seasonal variations, and health risks assessment of ambient air pollutants in the residential areas - W. C. Zhao; J. P. Cheng; Z. Y. Yu; Q. L. Tang; F. Cheng; Y. W. Yin; W. H. Wang (International Journal of Environmental Science and Technology, 2013)

RET and NRG1 interplay in Hirschsprung disease - Hongsheng Gui; Wai-Kiu Tang; Man-Ting So; Petroola Proitsi; Pak C. Sham; Paul K. Tam; Elly Sau-Wai Ngan; Stacey S. Cherny; Maria-Mercè Garcia-Barceló (Human Genetics, 2013)

A survey of viruses infecting Rosa spp. in New Zealand - E. J. M. Milleza; L. I. Ward; C. Delmiglio; J. Z. Tang; S. Veerakone; Z. Perez-Egusquiza (Australasian Plant Pathology, 2013)

Skin and soft-tissue infections caused by Aeromonas species - C. M. Chao; C. C. Lai; H. J. Tang; W. C. Ko; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

The comprehensive deformation retrieval for SAR interferometric data - L. Tao; H. Zhang; C. Wang; Y.X. Tang (International Journal of Remote Sensing, 2013)

Polysaccharides of Dendrobium officinale inhibit TNF-α-induced apoptosis in A-253 cell line - L. Xiang; C. W. Stephen Sze; T. B. Ng; Y. Tong; P. C. Shaw; C. W. Sydney Tang; Y. B. Kalin Zhang (Inflammation Research, 2013)

Effect of cholesterol on lipogenesis and VLDL–TG assembly and secretion in goose primary hepatocytes - C. C. Han; J. W. Wang; Z. X. Pan; H. Tang; S. X. Xiang; J. Wang; L. Li; F. Xu; S. H. Wei (Molecular and Cellular Biochemistry, 2013)

Biliary tract infections caused by Aeromonas species - C. M. Chao; C. C. Lai; H. J. Tang; W. C. Ko; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Trogia venenata (Agaricales), a novel poisonous species which has caused hundreds of deaths in southwestern China - Zhu L. Yang; Y. C. Li; L. P. Tang; G. Q. Shi; G. Zeng (Mycological Progress, 2012)

Utility and safety of procalcitonin in an antimicrobial stewardship program (ASP) in patients with malignancies - Y. X. Liew; W. Lee; Y. Y. Cai; J. Teo; S. S.-L. Tang; R. W.-Q. Ong; C. L.-L. Lim; P. B. Lingegowda; A. L.-H. Kwa; M. P. Chlebicki (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Deep placement of organic amendments in dense sodic subsoil increases summer fallow efficiency and the use of deep soil water by crops - J. S. Gill; G. J. Clark; P. W. Sale; R. R. Peries; C. Tang (Plant and Soil, 2012)

Mycobacterial infections in adult patients with hematological malignancy - C.-Y. Chen; W.-H. Sheng; C.-C. Lai; C.-H. Liao; Y.-T. Huang; W. Tsay; S.-Y. Huang; J.-L. Tang; H.-F. Tien; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Comparative Study of the Adsorption Selectivity of Cr(VI) onto Cationic Hydrogels with Different Functional Groups - Samuel C. N. Tang; Irene M. C. Lo; Mark S. H. Mak (Water, Air, & Soil Pollution, 2012)

Numerical Simulation of 3D Hydraulic Fracturing Based on an Improved Flow-Stress-Damage Model and a Parallel FEM Technique - L. C. Li; C. A. Tang; G. Li; S. Y. Wang; Z. Z. Liang; Y. B. Zhang (Rock Mechanics and Rock Engineering, 2012)

Polymorphism of 5′ regulatory region of ovine FSHR gene and its association with litter size in Small Tail Han sheep - M. X. Chu; X. H. Guo; C. J. Feng; Y. Li; D. W. Huang; T. Feng; G. L. Cao; L. Fang; R. Di; Q. Q. Tang; Y. H. Ma; K. Li (Molecular Biology Reports, 2012)

Robust multi-scale image matching for deriving ice surface velocity field from sequential satellite images - Hongxing Liu; Lei Wang; Sheng-Jung Tang; Kenneth C. Jezek (International Journal of Remote Sensing, 2012)

Formation and characteristics of post-earthquake debris flow: a case study from Wenjia gully in Mianzhu, Sichuan, SW China - H. Y. Ni; W. M. Zheng; Y. B. Tie; P. C. Su; Y. Q. Tang; R. G. Xu; D. W. Wang; X. Y. Chen (Natural Hazards, 2012)

Diversity of pneumococcal surface protein A (PspA) and relation to sequence typing in Streptococcus pneumoniae causing invasive disease in Chinese children - J. Qian; K. Yao; L. Xue; G. Xie; Y. Zheng; C. Wang; Y. Shang; H. Wang; L. Wan; L. Liu; C. Li; W. Ji; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Association between ATM 5557G>A polymorphism and breast cancer risk: a meta-analysis - Chen Mao; Vincent C. H. Chung; Ben-Fu He; Rong-Cheng Luo; Jin-Ling Tang (Molecular Biology Reports, 2012)

Developmental changes and regional localization of Dspp, Mepe, Mimecan and Versican in postnatal developing mouse teeth - C. Hou; Z. X. Liu; K. L. Tang; M. G. Wang; J. Sun; J. Wang; S. Li (Journal of Molecular Histology, 2012)

Ginsenoside-Rg1 mediates a hypoxia-independent upregulation of hypoxia-inducible factor-1α to promote angiogenesis - Kar-Wah Leung; Hoi-Man Ng; Maggie K. S. Tang; Chris C. K. Wong; Ricky N. S. Wong; Alice S. T. Wong (Angiogenesis, 2011)

A Numerical Investigation of Fracture Infilling and Spacing in Layered Rocks Subjected to Hydro-Mechanical Loading - L. C. Li; C. A. Tang; S. Y. Wang (Rock Mechanics and Rock Engineering, 2011)

In vivo speciation of zinc in Noccaea caerulescens in response to nitrogen form and zinc exposure - Alison C. Monsant; Peter Kappen; Yaodong Wang; Paul J. Pigram; Alan J. M. Baker; Caixian Tang (Plant and Soil, 2011)

Linkage analysis of plasma dopamine β-hydroxylase activity in families of patients with schizophrenia - Joseph F. Cubells; Xiangqing Sun; Wenbiao Li; Robert W. Bonsall; John A. McGrath; Dimitri Avramopoulos; Virginia K. Lasseter; Paula S. Wolyniec; Yi-Lang Tang; Kristina Mercer; Ann E. Pulver; Robert C. Elston (Human Genetics, 2011)

Clinical and microbiological characteristics of infections caused by various Nocardia species in Taiwan: a multicenter study from 1998 to 2010 - W. L. Liu; C. C. Lai; W. C. Ko; Y. H. Chen; H. J. Tang; Y. L. Huang; Y. T. Huang; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Effects of sediment size on transport capacity of overland flow on steep slopes - Guang-Hui Zhang; Li-Li Wang; Ke-Ming Tang; Rong-Ting Luo; X. C. Zhang (Hydrological Sciences Journal, 2011)

Sensitivity analysis of climatic parameters for sky classification - D. H. W. Li; H. L. Tang; K. L. Cheung; E. W. M. Lee; C. C. K. Cheng (Theoretical and Applied Climatology, 2011)

Extraction of tsunami source coefficients via inversion of DART $$^{\circledR}$$ buoy data - Donald B. Percival; Donald W. Denbo; Marie C. Eblé; Edison Gica; Harold O. Mofjeld; Michael C. Spillane; Liujuan Tang; Vasily V. Titov (Natural Hazards, 2011)

Conditions optimized for the preparation of single-stranded DNA (ssDNA) employing lambda exonuclease digestion in generating DNA aptamer - Marimuthu Citartan; Thean-Hock Tang; Soo-Choon Tan; Subash C. B. Gopinath (World Journal of Microbiology and Biotechnology, 2011)

Numerical simulation of the rock fragmentation process induced by two drill bits subjected to static and dynamic (impact) loading - S. Y. Wang; S. W. Sloan; H. Y. Liu; C. A. Tang (Rock Mechanics and Rock Engineering, 2011)

Rampant gene rearrangement and haplotype hypervariation among nematode mitochondrial genomes - Bradley C. Hyman; Samantha C. Lewis; Sha Tang; Zhen Wu (Genetica, 2011)

Long-term changes in phosphorus fractions in growers’ paddocks in the northern Victorian grain belt - D. T. Vu; R. D. Armstrong; P. J. Newton; C. Tang (Nutrient Cycling in Agroecosystems, 2011)

Numerical Study of Failure Mechanism of Serial and Parallel Rock Pillars - S. Y. Wang; S. W. Sloan; M. L. Huang; C. A. Tang (Rock Mechanics and Rock Engineering, 2011)

Paracoccus niistensis sp. nov., isolated from forest soil, India - Syed G. Dastager; C. K. Deepa; Wen-Jun Li; Shu-Kun Tang; Ashok Pandey (Antonie van Leeuwenhoek, 2011)

Buttress trees elevate soil heterogeneity and regulate seedling diversity in a tropical rainforest - Yong Tang; Xiaofei Yang; Min Cao; Carol C. Baskin; Jerry M. Baskin (Plant and Soil, 2011)

Fine mapping of the sunflower resistance locus Pl ARG introduced from the wild species Helianthus argophyllus - S. Wieckhorst; E. Bachlava; C. M. Dußle; S. Tang; W. Gao; C. Saski; S. J. Knapp; C.-C. Schön; V. Hahn; E. Bauer (Theoretical and Applied Genetics, 2010)

Nitrate nutrition enhances zinc hyperaccumulation in Noccaea caerulescens (Prayon) - Alison C. Monsant; Yaodong Wang; Caixian Tang (Plant and Soil, 2010)

Ecological Restoration of Polluted Plain Rivers Within the Haihe River Basin in China - W. Wang; X. Q. Tang; S. L. Huang; S. H. Zhang; C. Lin; D. W. Liu; H. J. Che; Q. Yang; Miklas Scholz (Water, Air, & Soil Pollution, 2010)

Electron microscopic visualization of asymmetric precursor translocation intermediates: SecA functions as a dimer - Ying Tang; XiJiang Pan; Phang C Tai; SenFang Sui (Science China Life Sciences, 2010)

Collection and Analysis of Expressed Sequence Tags Derived from Laser Capture Microdissected Switchgrass (Panicum virgatum L. Alamo) Vascular Tissues - Avinash C. Srivastava; Karuppaiah Palanichelvam; Junying Ma; Jarrod Steele; Elison B. Blancaflor; Yuhong Tang (BioEnergy Research, 2010)

Application of nitrogen in NO 3 − form increases rhizosphere alkalisation in the subsurface soil layers in an acid soil - C. Weligama; C. Tang; P. W. G. Sale; M. K. Conyers; D. L. Liu (Plant and Soil, 2010)

Inhibitory effects of potassium silicate on five soil-borne phytopathogenic fungi in vitro - G.-H. Shen; Q.-H. Xue; M. Tang; Q. Chen; L.-N. Wang; C.-M. Duan; L. Xue; J. Zhao (Journal of Plant Diseases and Protection, 2010)

Fine mapping of the 9q31 Hirschsprung’s disease locus - C. S. Tang; Y. Sribudiani; X. P. Miao; A. R. de Vries; G. Burzynski; M. T. So; Y. Y. Leon; B. H. Yip; J. Osinga; K. J. W. S. Hui; J. B. G. M. Verheij; S. S. Cherny; et al. (Human Genetics, 2010)

Correlation between Klebsiella pneumoniae carrying pLVPK-derived loci and abscess formation - H.-L. Tang; M.-K. Chiang; W.-J. Liou; Y.-T. Chen; H.-L. Peng; C.-S. Chiou; K.-S. Liu; M.-C. Lu; K.-C. Tung; Y.-C. Lai (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Comprehensive evaluation of municipal garbage disposal in Changchun City by the strategic environmental assessment - Jianling L. Xu; Zhanhui H. Tang; Jincheng C. Shang; Yuanhui H. Zhao (Environmental Science and Pollution Research, 2010)

Mutation analysis of the APC gene in Taiwanese FAP families: low incidence of APC germline mutation in a distinct subgroup of FAP families - J. M. Chiang; H. W. Chen; R. P. Tang; J. S. Chen; C. R. Changchien; P. S. Hsieh; J. Y. Wang (Familial Cancer, 2010)

A real‐time PCR for the detection of hepatopancreatic parvovirus (HPV) of penaeid shrimp - D C Yan; K F J Tang; D V Lightner (Journal of Fish Diseases, 2010)
Hepatopancreatic parvovirus (HPV) causes a common shrimp disease that occurs in many shrimp farming regions, especially in the Indo Pacific, and infects most of the cultured penaeid species. There are seven geographic HPV isolates known, so a method to detect different HPV types is needed. We developed a sensitive and generic real‐time PCR assay for the detection of HPV. A pair of primers and TaqMan probe based on an HPV sequence obtained from samples of Fenneropenaeus chinensis from Korea were selected, and they were used to amplify a 92 bp DNA fragment. This real‐time PCR was found to be specific to HPV and did not react with other shrimp viruses. A plasmid (pHPV‐2) containing the target HPV sequence was constructed and used for determination of the sensitivity of this assay. The assay could detect a single copy of plasmid DNA, and it was used successfully in finding HPV in shrimp samples from the China‐Yellow Sea region, Taiwan, Korea, Thailand, Madagascar, New Caledonia and Tanzania.

Endothelial dysfunction: a strategic target in the treatment of hypertension? - Eva H. C. Tang; Paul M. Vanhoutte (Pflügers Archiv - European Journal of Physiology, 2010)

A new species of Zygophiala associated with the flyspeck complex on apple from China - Yongqiang Ma; Rong Zhang; Guangyu Sun; Haixia Zhu; Ming Tang; Jean C. Batzer; Mark L. Gleason (Mycological Progress, 2010)

Development of delivery methods for carbohydrate-based drugs: controlled release of biologically-active short chain fatty acid-hexosamine analogs - Udayanath Aich; M. Adam Meledeo; Srinivasa-Gopalan Sampathkumar; Jie Fu; Mark B. Jones; Christopher A. Weier; Sung Yun Chung; Benjamin C. Tang; Ming Yang; Justin Hanes; Kevin J. Yarema (Glycoconjugate Journal, 2010)

Nitrate leaching stimulates subsurface root growth of wheat and increases rhizosphere alkalisation in a highly acidic soil - C. Weligama; P. W. G. Sale; M. K. Conyers; D. L. Liu; C. Tang (Plant and Soil, 2010)

Inverse association between serum 25(OH) vitamin D levels and non-melanoma skin cancer in elderly men - Jean Y. Tang; Neeta Parimi; Angela Wu; W. John Boscardin; James M. Shikany; Mary-Margaret Chren; Steven R. Cummings; Ervin H. Epstein; Douglas C. Bauer (Cancer Causes & Control, 2010)

Transformations and availability of phosphorus in three contrasting soil types from native and farming systems: A study using fractionation and isotopic labeling techniques - D. T. Vu; C. Tang; R. D. Armstrong (Journal of Soils and Sediments, 2010)

A distinct population of Saccharomyces cerevisiae in New Zealand: evidence for local dispersal by insects and human‐aided global dispersal in oak barrels - Matthew R. Goddard; Nicole Anfang; Rongying Tang; Richard C. Gardner; Casey Jun (Environmental Microbiology, 2010)
Summary Humans have used S. cerevisiae to make alcoholic beverages for at least 5000 years and now this super‐model research organism is central to advances in our biological understanding. Current models for S. cerevisiae suggest that its population comprises distinct domesticated and natural groups as well as mosaic strains, but we generally know little of the forces which shape its population structure. In order to test the roles that ecology and geography play in shaping the S. cerevisiae species we examined nine variable microsatellite loci in 172 strains of S. cerevisiae isolated from two spontaneous grape juice ferments, soil, flowers, apiaries and bark in New Zealand. Bayesian analysis shows that the S. cerevisiae in NZ comprise a subdivided but interbreeding population that out‐crosses ∼20% of the time. Some strains contributing to spontaneous ferments cluster with NZ soil/bark isolates, but others cluster with isolates from French oak barrels. It seems some strains have been globally dispersed by humans in oak barrels while some are locally vectored by insects. These data suggest geography is more important than ecology in shaping S. cerevisiae 's population structure.

Application of an Improved Flow-Stress-Damage Model to the Criticality Assessment of Water Inrush in a Mine: a Case Study - H. Q. Zhang; Y. N. He; C. A. Tang; Bashir Ahmad; L. J. Han (Rock Mechanics and Rock Engineering, 2009)

The role of hydraulic lift and subsoil P placement in P uptake of cotton (Gossypium hirsutum L.) - X. Wang; C. Tang; C. N. Guppy; P. W. G. Sale (Plant and Soil, 2009)

Circulating blood monocytes traffic to and participate in the periprosthetic tissue inflammation - Kai Zhang; Tang-Hong Jia; David McQueen; Wei-Ming Gong; David C. Markel; Paul H. Wooley; Shang-You Yang (Inflammation Research, 2009)

Antimicrobial stewardship program directed at broad-spectrum intravenous antibiotics prescription in a tertiary hospital - V. C. C. Cheng; K. K. W. To; I. W. S. Li; B. S. F. Tang; J. F. W. Chan; S. Kwan; R. Mak; J. Tai; P. Ching; P. L. Ho; W. H. Seto (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

At the Biological Modeling and Simulation Frontier - C. Anthony Hunt; Glen E. P. Ropella; Tai Ning Lam; Jonathan Tang; Sean H. J. Kim; Jesse A. Engelberg; Shahab Sheikh-Bahaei (Pharmaceutical Research, 2009)

Positive Allosteric Interaction of Structurally Diverse T-Type Calcium Channel Antagonists - Victor N. Uebele; Cindy E. Nuss; Steven V. Fox; Susan L. Garson; Razvan Cristescu; Scott M. Doran; Richard L. Kraus; Vincent P. Santarelli; Yuxing Li; James C. Barrow; Zhi-Qiang Yang; Kelly-Ann S. Schlegel; et al. (Cell Biochemistry and Biophysics, 2009)

Sequencing the Potato Genome: Outline and First Results to Come from the Elucidation of the Sequence of the World’s Third Most Important Food Crop - Richard G. F. Visser; Christian W. B. Bachem; Jan M. de Boer; Glenn J. Bryan; Swarup K. Chakrabati; Sergio Feingold; Robert Gromadka; Roeland C. H. J. van Ham; Sanwen Huang; Jeanne M. E. Jacobs; Boris Kuznetsov; Paulo E. de Melo; et al. (American Journal of Potato Research, 2009)

Atmospheric Aerosols over a Southwestern Region of Texas - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; Rafael Tadmor; T. C. Ho (Environmental Modeling & Assessment, 2009)

Expansion of CD14+CD16+ peripheral monocytes among patients with aseptic loosening - W. Wu; X. Zhang; C. Zhang; T. Tang; W. Ren; K. Dai (Inflammation Research, 2009)

Use of a novel anti-proliferative compound coated on a biopolymer to mitigate platelet-derived growth factor-induced proliferation in human aortic smooth muscle cells: comparison with sirolimus - Yong-Dan Tang; Ambarish Pandey; Antonina Kolmakova; Xin-Tong Wang; Subbu S. Venkatraman; Subroto Chatterjee; Freddy Y. C. Boey (Glycoconjugate Journal, 2009)

Comparison of Approaches to Calibrate a Surface Complexation Model for U(VI) Sorption to Weathered Saprolite - F. Zhang; J. C. Parker; S. C. Brooks; Y.-J. Kim; G. Tang; P. M. Jardine; D. B. Watson (Transport in Porous Media, 2009)

Workshop Report and Follow-Up—AAPS Workshop on Current Topics in GLP Bioanalysis: Assay Reproducibility for Incurred Samples—Implications of Crystal City Recommendations - Douglas M. Fast; Marian Kelley; C. T. Viswanathan; Jacqueline O’Shaughnessy; S. Peter King; Ajai Chaudhary; Russell Weiner; Anthony J. DeStefano; Daniel Tang (The AAPS Journal, 2009)

Construction, Characterization, and Expressed Sequence Tag (EST) Analysis of Normalized cDNA Library of Thermo-Photoperiod-Sensitive Genic Male Sterile (TPGMS) Wheat from Spike Developmental Stages - D. Yang; Z. H. Tang; L. P. Zhang; C. P. Zhao; Y. L. Zheng (Plant Molecular Biology Reporter, 2009)

Atmospheric Aerosol over a Southeastern Region of Texas: Chemical Composition and Possible Sources - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; T. C. Ho (Environmental Modeling & Assessment, 2009)

Rainfall-triggered debris flows following the Wenchuan earthquake - C. Tang; J. Zhu; W. L. Li; J. T. Liang (Bulletin of Engineering Geology and the Environment, 2009)

Modeling the Effects of Heterogeneity and Anisotropy on the Excavation Damaged/Disturbed Zone (EDZ) - S. H. Wang; C. I. Lee; P. G. Ranjith; C. A. Tang (Rock Mechanics and Rock Engineering, 2009)

Physiological and biochemical responses of in vitro Fusarium oxysporum f.sp. niveum to benzoic acid - H. -S. Wu; Y. Wang; C. -Y. Zhang; M. Gu; Y. -X. Liu; G. Chen; J. -H. Wang; Z. Tang; Z. -S. Mao; Q. -R. Shen (Folia Microbiologica, 2009)

Comparative Analyses of Coding and Noncoding DNA Regions Indicate that Acropora (Anthozoa: Scleractina) Possesses a Similar Evolutionary Tempo of Nuclear vs. Mitochondrial Genomes as in Plants - I.-Ping Chen; Chung-Yu Tang; Chih-Yung Chiou; Jia-Ho Hsu; Nuwei Vivian Wei; Carden C. Wallace; Paul Muir; Henry Wu; Chaolun Allen Chen (Marine Biotechnology, 2009)

Bombyx mori nucleopolyhedrovirus ORF51 encodes a budded virus envelope associated protein - C.-H. Tian; X.-D. Tang; H.-J. Xu; J.-Q. Ge; Y.-G. Miao; C.-X. Zhang (Virus Genes, 2009)

Subsurface microbiology and biogeochemistry of a deep, cold‐water carbonate mound from the Porcupine Seabight (IODP Expedition 307) - Gordon Webster; Anna Blazejak; Barry A. Cragg; Axel Schippers; Henrik Sass; Joachim Rinna; Xiaohong Tang; Falko Mathes; Timothy G. Ferdelman; John C. Fry; Andrew J. Weightman; R. John Parkes (Environmental Microbiology, 2009)
Summary The Porcupine Seabight Challenger Mound is the first carbonate mound to be drilled (∼270 m) and analyzed in detail microbiologically and biogeochemically. Two mound sites and a non‐mound Reference site were analyzed with a range of molecular techniques [catalyzed reporter deposition‐fluorescence in situ hybridization (CARD‐FISH), quantitative PCR (16S rRNA and functional genes, dsrA and mcrA ), and 16S rRNA gene PCR‐DGGE] to assess prokaryotic diversity, and this was compared with the distribution of total and culturable cell counts, radiotracer activity measurements and geochemistry. There was a significant and active prokaryotic community both within and beneath the carbonate mound. Although total cell numbers at certain depths were lower than the global average for other subseafloor sediments and prokaryotic activities were relatively low (iron and sulfate reduction, acetate oxidation, methanogenesis) they were significantly enhanced compared with the Reference site. In addition, there was some stimulation of prokaryotic activity in the deepest sediments (Miocene, > 10 Ma) including potential for anaerobic oxidation of methane activity below the mound base. Both Bacteria and Archaea were present, with neither dominant, and these were related to sequences commonly found in other subseafloor sediments. With an estimate of some 1600 mounds in the Porcupine Basin alone, carbonate mounds may represent a significant prokaryotic subseafloor habitat.

Determination of ocean primary productivity using support vector machines - S. Tang; C. Chen; H. Zhan; T. Zhang (International Journal of Remote Sensing, 2008)

An appraisal of surface chlorophyll estimation by satellite remote sensing in the South China Sea - S. Tang; C. Chen; H. Zhan; J. Zhang; J. Yang (International Journal of Remote Sensing, 2008)

Genetic analysis of photoperiod sensitivity in a tropical by temperate maize recombinant inbred population using molecular markers - C. L. Wang; F. F. Cheng; Z. H. Sun; J. H. Tang; L. C. Wu; L. X. Ku; Y. H. Chen (Theoretical and Applied Genetics, 2008)

Phosphorus acquisition characteristics of cotton (Gossypium hirsutum L.), wheat (Triticum aestivum L.) and white lupin (Lupinus albus L.) under P deficient conditions - X. Wang; C. Tang; C. N. Guppy; P. W. G. Sale (Plant and Soil, 2008)

Localised nitrate and phosphate application enhances root proliferation by wheat and maximises rhizosphere alkalisation in acid subsoil - C. Weligama; C. Tang; P. W. G. Sale; M. K. Conyers; D. L. Liu (Plant and Soil, 2008)

LRRK2 R1628P increases risk of Parkinson’s disease: replication evidence - E. K. Tan; Louis C. Tan; H. Q. Lim; R. Li; M. Tang; Yuen Yih; R. Pavanni; K. M. Prakash; S. Fook-Chong; Yi Zhao (Human Genetics, 2008)

Genome-wide distribution of ancestry in Mexican Americans - Analabha Basu; Hua Tang; Xiaofeng Zhu; C. Charles Gu; Craig Hanis; Eric Boerwinkle; Neil Risch (Human Genetics, 2008)

Simulation of direct effects of black carbon aerosol on temperature and hydrological cycle in Asia by a Regional Climate Model - J. Wu; C. Fu; Y. Xu; J. P. Tang; W. Wang; Z. Wang (Meteorology and Atmospheric Physics, 2008)

Ecology of seed germination of eight non-pioneer tree species from a tropical seasonal rain forest in southwest China - Yang Yu; Jerry M. Baskin; Carol C. Baskin; Yong Tang; Min Cao (Plant Ecology, 2008)

Deformation retrieval in large areas based on multibaseline DInSAR algorithm: a case study in Cangzhou, northern China - T. Wu; C. Wang; H. Zhang; Y. X. Tang; L. Tian (International Journal of Remote Sensing, 2008)

Quantitative Structure–Activity Relationships for Predicting the Joint Toxicity of Substituted Anilines and Phenols to Algae - G. H. Lu; C. Wang; Z. Y. Tang; X. L. Guo (Bulletin of Environmental Contamination and Toxicology, 2008)

A method for retrieving soil moisture in Tibet region by utilizing microwave index from TRMM/TMI data - K. B. Mao; H. J. Tang; L. X. Zhang; M. C. Li; Y. Guo; D. Z. Zhao (International Journal of Remote Sensing, 2008)

Input–Output Budgets for Inorganic Nitrogen Under Acid Rain in a Subtropical Evergreen Mixed Forest in Central-South China - C. Y. Du; G. M. Zeng; G. Zhang; L. Tang; X. D. Li; D. L. Huang; L. Huang; Y. M. Jiang (Water, Air, & Soil Pollution, 2008)

Influence of mouse genetic background on wear particle-induced in vivo inflammatory osteolysis - C. Zhang; T. Tang; W. Ren; X. Zhang; K. Dai (Inflammation Research, 2008)

Fine mapping of a major quantitative trait loci, qSSP7, controlling the number of spikelets per panicle as a single Mendelian factor in rice - Y. Z. Xing; W. J. Tang; W. Y. Xue; C. G. Xu; Qifa Zhang (Theoretical and Applied Genetics, 2008)

Changes and availability of P fractions following 65 years of P application to a calcareous soil in a Mediterranean climate - D. T. Vu; C. Tang; R. D. Armstrong (Plant and Soil, 2008)

DH1, a LOB domain-like protein required for glume formation in rice - A. Li; Y. Zhang; X. Wu; W. Tang; R. Wu; Z. Dai; G. Liu; H. Zhang; C. Wu; G. Chen; X. Pan (Plant Molecular Biology, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Comparison of four infectious bursal disease viruses isolated from different bird species - Y. S. Wang; Z. C. Wang; Y. D. Tang; Z. L. Shi; K. W. He; Y. Li; J. B. Hou; H. C. Yao; H. J. Fan; C. P. Lu (Archives of Virology, 2007)

Allomermis solenopsi n. sp. (Nematoda: Mermithidae) parasitising the fire ant Solenopsi s invicta Buren (Hymenoptera: Formicidae) in Argentina - George O. Poinar; Sanford D. Porter; Sha Tang; Bradley C. Hyman (Systematic Parasitology, 2007)

Changes in phosphorus fractions, sorption and release in Udic Mollisols under different ecosystems - C. Song; X. Z. Han; C. Tang (Biology and Fertility of Soils, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Extraction of Trigonella foenum-graecum L. by supercritical fluid CO2 and its contact toxicity to Rhyzopertha dominica (Fabricius) (Coleoptera: Bostrichidae) - G. W. Tang; C. J. Yang; L. D. Xie (Journal of Pest Science, 2007)

Ganoderma lucidum polysaccharide peptide reduced the production of proinflammatory cytokines in activated rheumatoid synovial fibroblast - Y. W. Ho; J. S. L. Yeung; P. K. Y. Chiu; W. M. Tang; Z. B. Lin; R. Y. K. Man; C. S. Lau (Molecular and Cellular Biochemistry, 2007)

Quantitative Structure–Activity Relationships for Predicting the Joint Toxicity of Substituted Anilines and Phenols to Algae - G. H. Lu; C. Wang; Z. Y. Tang; X. L. Guo (Bulletin of Environmental Contamination and Toxicology, 2007)

Quantitative Structure–Activity Relationships for Predicting the Joint Toxicity of Substituted Anilines and Phenols to Algae - G. H. Lu; C. Wang; Z. Y. Tang; X. L. Guo (Bulletin of Environmental Contamination and Toxicology, 2007)

Modulation of the suppressive effect of corticosterone on adult rat hippocampal cell proliferation by paroxetine - Guang Qiu; Daiga M. Helmeste; Asanka N. Samaranayake; Wui-Man Lau; Tatia M. C. Lee; Siu-Wa Tang; Kwok-Fai So (Neuroscience Bulletin, 2007)

Phylogenetic utility of protein (RPB2, β-tubulin) and ribosomal (LSU, SSU) gene sequences in the systematics of Sordariomycetes (Ascomycota, Fungi) - Alvin M. C. Tang; Rajesh Jeewon; Kevin D. Hyde (Antonie van Leeuwenhoek, 2007)

Numerical Modelling of the Heterogeneous Rock Fracture Process Using Various Test Techniques - H. Y. Liu; S. Q. Kou; P.-A. Lindqvist; C. A. Tang (Rock Mechanics and Rock Engineering, 2007)

Abnormal expressions of the subunits of the UDP-N-acetylglucosamine: lysosomal enzyme, N-acetylglucosamine-1-phosphotransferase, result in the formation of cytoplasmic vacuoles resembling those of the I-cells - Cecilia Y. S. Ho; Nelson L. S. Tang; Ava K. Y. Yeung; Abby K. C. Lau; Joannie Hui; Anthony W. I. Lo (Journal of Molecular Medicine, 2007)

The LRRK2 Gly2385Arg variant is associated with Parkinson’s disease: genetic and functional evidence - E. K. Tan; Y. Zhao; L. Skipper; M. G. Tan; A. Di Fonzo; L. Sun; S. Fook-Chong; S. Tang; E. Chua; Y. Yuen; L. Tan; R. Pavanni; et al. (Human Genetics, 2007)

Temporal and spatial responses of Chironomidae (Diptera) and other benthic invertebrates to urban stormwater runoff - Susan E. Gresens; Kenneth T. Belt; Jamie A. Tang; Daniel C. Gwinn; Patricia A. Banks (Hydrobiologia, 2007)

Enhanced stress tolerance in transgenic pine expressing the pepper CaPF1 gene is associated with the polyamine biosynthesis - Wei Tang; R. J. Newton; C. Li; T. M. Charles (Plant Cell Reports, 2006)

Analytical and Numerical Study on the Pillar Rockbursts Mechanism - S. Y. Wang; K. C. Lam; S. K. Au; C. A. Tang; W. C. Zhu; T. H. Yang (Rock Mechanics and Rock Engineering, 2006)

Requirement for pre-existing of p21 to prevent doxorubicin-induced apoptosis through inhibition of caspase-3 activation - J. J. Tang; C. Shen; Y. J. Lu (Molecular and Cellular Biochemistry, 2006)

Genome-wide linkage scans for loci affecting total cholesterol, HDL-C, and triglycerides: the Family Blood Pressure Program - Suzette J. Bielinski; Weihong Tang; James S. Pankow; Michael B. Miller; Thomas H. Mosley; Eric Boerwinkle; Richard A. Olshen; J. David Curb; Cashell E. Jaquish; D. C. Rao; Alan Weder; Donna K. Arnett (Human Genetics, 2006)

Identification and mapping of Rf-I an inhibitor of the Rf5 restorer gene for Cms-C in maize (Zea mays L.) - Y. M. Hu; J. H. Tang; H. Yang; H. L. Xie; X. M. Lu; J. H. Niu; W. C. Chen (Theoretical and Applied Genetics, 2006)

Racial admixture and its impact on BMI and blood pressure in African and Mexican Americans - Hua Tang; Eric Jorgenson; Maya Gadde; Sharon L. R. Kardia; D. C. Rao; Xiaofeng Zhu; Nicholas J. Schork; Craig L. Hanis; Neil Risch (Human Genetics, 2006)

Body Size and Risk of Epithelial Ovarian Cancer (United States) - Mary Anne Rossing; Mei-Tzu C. Tang; Elaine W. Flagg; Linda K. Weiss; Kristine G. Wicklund; Noel S. Weiss (Cancer Causes & Control, 2006)

Caspase 3, periodically expressed and activated at G2/M transition, is required for nocodazole-induced mitotic checkpoint - S.-L. Hsu; C. -T. R. Yu; S. -C. Yin; M. -J. Tang; A. -C. Tien; Y. -M. Wu; C. -Y. F. Huang (Apoptosis, 2006)

Genetic Erosion from Modern Varieties into Traditional Upland Rice Cultivars (Oryza sativa L.) in Northern Thailand - R. Ishikawa; S. Yamanaka; Y. Fukuta; S. Chitrakon; C. Bounphanousay; K. Kanyavong; L.-H. Tang; I. Nakamura; T. Sato; Y.-I. Sato (Genetic Resources and Crop Evolution, 2006)

Mapping the RNA-binding domain on the DpCPV VP4 - S. L. Zhao; C. Y. Liang; W. J. Zhang; X. C. Tang; H. Y. Peng (Archives of Virology, 2006)

Interactions Between High pH and Iron Supply on Nodulation and Iron Nutrition of Lupinus albus L. Genotypes Differing in Sensitivity to Iron Deficiency - C. Tang; S. J. Zheng; Y. F. Qiao; G. H. Wang; X. Z. Han (Plant and Soil, 2006)

Population stratification confounds genetic association studies among Latinos - Shweta Choudhry; Natasha E. Coyle; Hua Tang; Keyan Salari; Denise Lind; Suzanne L. Clark; Hui-Ju Tsai; Mariam Naqvi; Angie Phong; Ngim Ung; Henry Matallana; Pedro C. Avila; et al. (Human Genetics, 2006)

Industrial wideband noise reduction for hearing aids using a headset with adaptive-feedback active noise cancellation - J. -H. Lin; P. -C. Li; S. -T. Tang; P. -T. Liu; S. -T. Young (Medical & Biological Engineering & Computing, 2005)

PAQR Proteins: A Novel Membrane Receptor Family Defined by an Ancient7-Transmembrane Pass Motif - Y. Tom Tang; Tianhua Hu; Matthew Arterburn; Bryan Boyle; Jessica M. Bright; Peter C. Emtage; Walter D. Funk (Journal of Molecular Evolution, 2005)

Identification and validation of QTL for Sclerotinia midstalk rot resistance in sunflower by selective genotyping - Z. Micic; V. Hahn; E. Bauer; A. E. Melchinger; S. J. Knapp; S. Tang; C. C. Schön (Theoretical and Applied Genetics, 2005)

Phosphorus characteristics correlate with soil fertility of albic luvisols - X. Z. Han; C. Tang; C. Y. Song; S. Y. Wang; Y. F. Qiao (Plant and Soil, 2005)

On Tension Failure of 2-D Rock Specimens and Associated Acoustic Emission - L. G. Tham; H. Liu; C. A. Tang; P. K. K. Lee; Y. Tsui (Rock Mechanics and Rock Engineering, 2005)

Influence of phenolic acids on phosphorus mobilisation in acidic and calcareous soils - H. Hu; C. Tang; Z. Rengel (Plant and Soil, 2005)

The persistence of ripe fleshy fruits in the presence and absence of frugivores - Alvin M. C. Tang; Richard T. Corlett; Kevin D. Hyde (Oecologia, 2005)

Expression of the grapevine stilbene synthase gene VST1 in papaya provides increased resistance against diseases caused by Phytophthora palmivora - Yun J. Zhu; Ricelle Agbayani; Mel C. Jackson; C. S. Tang; Paul H. Moore (Planta, 2004)

QTL mapping of Sclerotinia midstalk-rot resistance in sunflower - Z. Micic; V. Hahn; E. Bauer; C. C. Schn; S. J. Knapp; S. Tang; A. E. Melchinger (Theoretical and Applied Genetics, 2004)

Acidic-rich region of amyloid precursor protein induces glial cell apoptosis - K.-H. Sun; G.-H. Sun; Y. Su; C.-I. Chang; M.-J. Chuang; W.-L. Wu; C.-Y. Chu; S.-J. Tang (Apoptosis, 2004)

Influence of Heterogeneity of Mechanical Properties on Hydraulic Fracturing in Permeable Rocks - T. H. Yang; L. G. Tham; C. A. Tang; Z. Z. Liang; Y. Tsui (Rock Mechanics and Rock Engineering, 2004)

Cigarette Smoking Among Lesbians, Gays, and Bisexuals: How Serious a Problem? (United States) - Hao Tang; Greg L. Greenwood; David W. Cowling; Jon C. Lloyd; April G. Roeseler; Dileep G. Bal (Cancer Causes & Control, 2004)

The Effect of Different Plant Growth Regulators on Adventitious Shoot Formation from Virginia Pine (Pinus virginiana) Zygotic Embryo Explants - Wei Tang; Latoya C. Harris; Vilay Outhavong; Ronald J. Newton (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Combined effects of waterlogging and salinity on electrochemistry, water-soluble cations and water dispersible clay in soils with various salinity levels - S.G. Lu; C. Tang; Z. Rengel (Plant and Soil, 2004)

Lymphocyte surge as a marker for immunorestitution disease due to Pneumocystis jiroveci pneumonia in HIV-negative immunosuppressed hosts - V. C. C. Cheng; I. F. N. Hung; A. K. L. Wu; B. S. F. Tang; C. M. Chu; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Calcium, magnesium and microelement uptake as affected by phosphorus sources and interspecific root interactions between wheat and chickpea - L. Li; C. Tang; Z. Rengel; F.S. Zhang (Plant and Soil, 2004)

Proton release of two genotypes of bean (Phaseolus vulgaris L.) as affected by N nutrition and P deficiency - C. Tang; J.J. Drevon; B. Jaillard; G. Souche; P. Hinsinger (Plant and Soil, 2004)

Root-induced acidification and excess cation uptake by N2-fixing Lupinus albus grown in phosphorus-deficient soil - J. Shen; C. Tang; Z. Rengel; F. Zhang (Plant and Soil, 2004)

Micromechanical Model for Simulating the Fracture Process of Rock - W. C. Zhu; C. A. Tang (Rock Mechanics and Rock Engineering, 2004)

Inclusion Effects of Highly Water-Soluble Cyclodextrins on the Solubility, Photodegradation, and Acute Toxicity of Methyl Parathion - Q. Zeng; B. Liao; Y. Luo; C. Liu; H. Tang (Bulletin of Environmental Contamination and Toxicology, 2003)

Modelling the distribution, sustainability and diapause emergence timing of the copepod Calanus finmarchicus in the Labrador Sea - D. P. Tittensor; B. DeYoung; C. L. Tang (Fisheries Oceanography, 2003)
It is now recognized that Calanus finmarchicus , the dominant copepod zooplankter of the North Atlantic, has most of its biomass in the open ocean. While the Labrador Sea does contain a large population of Calanus finmarchicus , the importance of possible connections with the rest of the North Atlantic are not understood. Although there are few wintertime observations, sufficient data exist to model the role of the circulation, temperature and food supply on population dynamics. This study couples a biological model of Calanus finmarchicus with a physical oceanographic model of the Labrador Sea, using chlorophyll data derived from observations by the satellite‐borne SeaWiFS (Sea‐viewing Wide Field‐of‐view Sensor) as a proxy food supply for the numerical copepods. We produce a large‐scale, comprehensive picture of the spatial distribution of Calanus finmarchicus in the Labrador Sea, along with an exploration of the timing of diapause and an examination of population sustainability. We are able to simulate reasonably well the temporal and spatial patterns of Calanus finmarchicus in the Labrador Sea. During a year long model run, the population has a single generation over most of the Labrador Sea, with a final diapausing population about 50% the size of the initial for the parameters used in these simulations. A latitudinally dependent diapause emergence scheme with early emergence to the south of Newfoundland provides the best fit to data. A change of 0.5°C in the temperature field can cause significant changes in the population abundance in a single year, due to changes in Calanus finmarchicus growth rates.

Modelling yield losses of aluminium-resistant and aluminium-sensitive wheat due to subsurface soil acidity: effects of rainfall, liming and nitrogen application - C. Tang; S. Asseng; E. Diatloff; Z. Rengel (Plant and Soil, 2003)

Himalayan magmatism and porphyry copper-molybdenum mineralization in the Yulong ore belt, East Tibet - X. X. Gu; J. X. Tang; C. S. Wang; J. P. Chen; B. B. He (Mineralogy and Petrology, 2003)

Orthogonal polynomial models to describe yield response of rice to nitrogen and phosphorus at different levels of soil fertility - F. Zhang; J. Shen; R. Li; Z. Rengel; C. Tang (Nutrient Cycling in Agroecosystems, 2003)

Role of phosphorus nutrition in development of cluster roots and release of carboxylates in soil-grown Lupinus albus - J. Shen; Z. Rengel; C. Tang; F. Zhang (Plant and Soil, 2003)

Groundwater flow and geochemistry in the lower reaches of the Yellow River: a case study in Shandang Province, China - Chen J.; Tang C.; Sakura Y.; Kondoh A.; Shen Y. (Hydrogeology Journal, 2002)

Screening rough-seeded lupins (Lupinus pilosus Murr. and Lupinus atlanticus Glads.) for tolerance to calcareous soils - J. D. Brand; C. Tang; A. J. Rathjen (Plant and Soil, 2002)

Growth response to subsurface soil acidity of wheat genotypes differing in aluminium tolerance - C. Tang; E. Diatloff; Z. Rengel; B. McGann (Plant and Soil, 2001)

Suitability of hydroxyapatite and iron phosphate as P sources for Lupinus albus grown in nutrient solution - L. Sas; C. Tang; Z. Rengel (Plant and Soil, 2001)

Impact of nitrogen form on iron uptake and distribution in maize seedlings in solution culture - C. Zou; J. Shen; F. Zhang; S. Guo; Z. Rengel; C. Tang (Plant and Soil, 2001)

A simple and rapid procedure to establish embryogenic cell suspensions as a source of protoplasts for efficient plant regeneration from two Chinese commercial rice cultivars - K. Tang; X. Sun; D. An; J. B. Power; E. C. Cocking; M. R. Davey (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Cultivar variation in the effect of chlorsulfuron in depressing the uptake of copper in wheat - C. Tang; A. D. Robson (Plant and Soil, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

The effect of soil moisture on the tolerance of Lupinus pilosus genotypes to a calcareous soil - J.D. Brand; C. Tang; R.D. Graham (Plant and Soil, 2000)

A critical review on methods to measure apoplastic pH in plants - Q. Yu; C. Tang; J. Kuo (Plant and Soil, 2000)

Impact of chemical composition of legume residues and initial soil pH on pH change of a soil after residue incorporation - C. Tang; Q. Yu (Plant and Soil, 1999)

Particle-bombardment-mediated co-transformation of elite Chinese rice cultivars with genes conferring resistance to bacterial blight and sap-sucking insect pests - Kexuan Tang; Porntip Tinjuangjun; Yanan Xu; Xiaofen Sun; John A. Gatehouse; Pamela C. Ronald; Huaxiong Qi; Xinggui Lu; Paul Christou; Ajay Kohli (Planta, 1999)

Synthesis and diversity analysis of lead discovery piperazine-2-carboxamide libraries - Timothy F. Herpin; George C. Morton; Allison K. Dunn; Cedric Fillon; Paul R. Menard; Sheng Yu Tang; Joseph M. Salvino; Richard F. Labaudinière (Molecular Diversity, 1998)

Identification and genetic characterization of yeasts isolated from freshwater prawns, Macrobrachium rosenbergii de Man, in Taiwan - C C Lu; K F J Tang; S N Chen (Journal of Fish Diseases, 1998)
Since 1987, farmers in southern Taiwan have reported significant disease‐related mortalities in freshwater prawns. Most mortalities have occurred during the winter, and usually almost all the adult prawns die within 4–5 days after clinical signs appear. Histopathological studies show that cells in hepatopancreatic ducts and tubules are vacuolized and degenerated. Large numbers of membrane‐bound yeast aggregates are observed in the affected tissues. Two hundred and seventeen yeast isolates were obtained from diseased prawns, pond water and sediments from six areas. DNA restriction fragment length polymorphism (RFLP) was used to analyse the yeast genomes and to categorize them into five groups. Conventional biochemical and metabolic methods were then used to identify the yeasts of each group. The results showed that two strains of Candida sake (I and II), Pichia anomala, Endomyces fibuliger and Candida famata were present. In addition, the RAPD (random amplified polymorphic DNA) method was used to determine their genomic similarities. Two strains (I and II) of C. sake were the most similar (72%). C. sake I appears to be the primary causative agent of disease, based on frequencies of occurrence of the yeasts found in the diseased prawns.

Intranigral ventral mesencephalic grafts and nigrostriatal injections of glial cell line-derived neurotrophic factor restore dopamine release in the striatum of 6-hydroxydopamine-lesioned rats - F. I. Tang; L. T. Tien; F. C. Zhou; B. J. Hoffer; Y. Wang (Experimental Brain Research, 1998)

Factors affecting soil acidification under legumes I. Effect of potassium supply - C. Tang (Plant and Soil, 1998)

Geochemistry of HCO3 − at the sediment-water interface of lakes from the Southwestern Chinese plateau - F. C. Wu; H. R. Qing; G. J. Wan; D. G. Tang; R. G. Huang; Y. R. Cal (Water, Air, & Soil Pollution, 1997)

A Theoretical Model for Kaiser Effect in Rock - C. A. Tang; Z. H. Chen; X. H. Xu; C. Li (Pure and Applied Geophysics, 1997)

Murine Hn1 on Chromosome 11 is expressed in hemopoietic and brain tissues - Wozhan Tang; Yong-Hong Lai; Xiao-Dong Han; Peter M. C. Wong; Luanne L. Peters; David H. K. Chui (Mammalian Genome, 1997)

Light and electron microscopic evidence of white spot disease in the giant tiger shrimp, Penaeus monodon (Fabricius), and the kuruma shrimp, Penaeus japonicus (Bate), cultured in Taiwan - C S Wang; K F J Tang; G H Kou; S N Chen (Journal of Fish Diseases, 1997)
Since 1992, mass mortalities among cultured giant tiger shrimp, Penaeus monodon (Fabricius), and kuruma shrimp, Penaeus japonicus (Bate), have been observed in Taiwan. The condition is known as ‘white spot disease’ (WSD), based on the characteristic white spots on the cuticle of diseased shrimp. With the scanning electron microscope, two sizes of white spots were observed. Each spot represented a protrusion on the inside surface of the carapace. The composition of white spots was similar to that of the cuticule, most calcium, as determined with an energy dispersive spectrometer. Histological studies of moribund, infected specimens revealed degenerated cells, characterized by hypertrophied nuclei, in various meso‐ and ectodermal tissues. Infected tissues included cuticular epidermis, connective tissue, lymphoid organ, antennal gland, and haematopoietic, gill and nervous tissue. Nuclei were Feulgen‐positive and no occlusion body was found in the necrotic tissue. Transmission electron microscopy revealed the presence of rod‐shaped and enveloped virions in the hypertrophied nuclei. The virions measured 298 ± 21 × 107 ± 8 nm in the giant tiger shrimp and 248 ± 12 × 104 ± 8 nm in the kuruma shrimp. In an experimental infection trial, cumulative mortality was 40% within 14 days under stress conditions. No mortality was observed in controls or in non‐stressed infected shrimp. Experimental infections show that environmental stressors such as ammonia may enhance the severity of WSD virus infections in cultured shrimp.

Use of the Intestinal Bile Acid Transporter for the Uptake of Cholic Acid Conjugates with HIV-1 Protease Inhibitory Activity - Matts Kågedahl; Peter W. Swaan; Carl T. Redemann; Mary Tang; Charles S. Craik; Francis C. Szoka; Svein Øie (Pharmaceutical Research, 1997)

Spontaneous N,N '-Dibutylurea (DBU) Formation in Benlate DF® Formulation Under Elevated Temperatures - C. S. Tang; L.-W. Song (Archives of Environmental Contamination and Toxicology, 1996)

Spontaneous N,N′-dibutylurea (DBU) formation in benlate DF® formulation under elevated temperatures - C. S. Tang; L. W. Song (Archives of Environmental Contamination and Toxicology, 1996)

Envelope gene sequences of human T-lymphotropic virus type I in Taiwan - M. T. Lin; Y. C. Chen; P. J. Chen; Y. C. Yang; J. L. Tang; J. M. Wu; S. E. Chuang; C. S. Yang (Archives of Virology, 1996)

Genetic control of polyketide biosynthesis in the genusStreptomyces - C. Richard Hutchinson; Heinrich Decker; Krishnamurthy Madduri; Sharee L. Otten; Li Tang (Antonie van Leeuwenhoek, 1994)

Effects of immunization with the p12 proteins of LP-BM5 defective and ecotropic viruses on development of MAIDS - Yao Tang; A. W. Hügin; Janet W. Hartley; Torgny N. Fredrickson; H. C. Morse; Sisir K. Chattopadhyay (Archives of Virology, 1993)

1-Butyl isocyanate from aqueous benlate formulations - C. S. Tang; K. Yanagihara; Y. Zhang (Archives of Environmental Contamination and Toxicology, 1993)

1-butyl isocyanate from aqueous Benlate formulations - C. S. Tang; K. Yanagihara; Y. Zhang (Archives of Environmental Contamination and Toxicology, 1992)

Electron microscopic evidence for the association of M 2 protein with the influenza virion - D. C. Jackson; Xi-Lin Tang; K. Gopal Murti; R. G. Webster; G. W. Tregear; W. J. Bean (Archives of Virology, 1991)

Factors affecting pathogenicity of NPV preparations to the corn earworm,Heliothis armigera - S. J. Tuan; L. C. Tang; R. F. Hou (BioControl, 1989)

Human stomach alcohol and aldehyde dehydrogenases (ALDH): A genetic model proposed for ALDH III isozymes - S. -J. Yin; T. -C. Cheng; C. -P. Chang; Y. -J. Chen; Y. -C. Chao; H. -S. Tang; T. -M. Chang; C. -W. Wu (Biochemical Genetics, 1988)

Human stomach alcohol and aldehyde dehydrogenases (ALDH): A genetic model proposed for ALDH III isozymes - S. -J. Yin; T. -C. Cheng; C. -P. Chang; Y. -J. Chen; Y. -C. Chao; H. -S. Tang; T. -M. Chang; C. -W. Wu (Biochemical Genetics, 1988)